Process for preparing silicon-containing composite particles

JP2025041698AActive Publication Date: 2025-03-26WACKER CHEMIE AG +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024216467
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-11-30
Filing Date
2024-12-11
Publication Date
2025-03-26
Estimated Expiration
2041-10-22

AI Technical Summary

Benefits of technology

は、ケイ素をミクロ細孔およびより小さいメソ細孔に収容することによって実質的に得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025041698000001_ABST
    Figure 2025041698000001_ABST
Patent Text Reader

Abstract

To provide a process for preparing silicon-containing composite particles suitable for use as anode active materials in lithium-ion batteries.SOLUTION: The process comprises the steps of: (a) providing a plurality of porous particles comprising micropores and / or mesopores, where (i) the D50 particle diameter of the porous particles is 0.5 to 200 μm, (ii) the total pore volume of micropores and mesopores measured by gas adsorption is 0.4 to 2.2 cm3 / g, and (iii) the PD50 pore diameter measured by gas adsorption is 30 nm or less; (b) combining a charge of the porous particles with a charge of a silicon-containing precursor in a batch pressure reactor, where the charge of porous particles has a volume of at least 20 cm3 per liter of reactor volume, and where the charge of the silicon-containing precursor comprises at least 2 g of silicon per liter of reactor volume; and (c) heating the reactor to a temperature effective to cause deposition of silicon in the pores of the porous particles, thereby providing the silicon-containing composite particles.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to a method for producing silicon-containing composite particles by depositing silicon within the pores of porous particles. The silicon-containing composite particles are generally suitable for use as negative electrode active materials in metal ion secondary batteries. [Background technology]

[0002] Rechargeable metal-ion batteries are widely used in portable electronic devices such as mobile phones and laptops, and are increasingly being applied to electric and hybrid vehicles. Rechargeable metal-ion batteries generally contain a negative electrode in the form of a metal current collector provided with a layer of electroactive material, defined as a material capable of inserting and releasing metal ions during charging and discharging of the battery. The terms "positive electrode" and "negative electrode" are used herein in the sense that the battery is placed across a load such that the negative electrode is the negative electrode. When a metal-ion battery is charged, metal ions are transported from the metal-ion-containing positive electrode layer through the electrolyte to the negative electrode and are inserted into the negative electrode material. The term "battery" is used herein to refer to both devices containing a single positive electrode and a single negative electrode, and devices containing multiple positive electrodes and / or multiple negative electrodes.

[0003] There is interest in improving the gravimetric and / or volumetric capacity of rechargeable metal-ion batteries. To date, commercially available lithium-ion batteries have been limited to those using graphite as the anode active material. When a graphite anode is charged, lithium intercalates between the graphite layers and is expressed by the empirical formula Li x C6, where x is greater than 0 and less than or equal to 1. As a result, graphite has a maximum theoretical capacity of 372 mAh / g in lithium-ion batteries, with practical capacities somewhat lower (approximately 340-360 mAh / g). Other materials, such as silicon, tin, and germanium, can intercalate lithium at significantly higher capacities than graphite, but are not yet in widespread commercial use due to the difficulty of maintaining sufficient capacity over many charge-discharge cycles.

[0004] In particular, silicon has been recognized as a promising alternative to graphite in the manufacture of rechargeable metal-ion batteries with high gravimetric and volumetric capacities due to its very high capacity relative to lithium (see, for example, Insertion Electrode Materials for Rechargeable Lithium Batteries, Winter, M. et al. in Adv. Mater. 1998, 10, No. 10). At room temperature, silicon has a theoretical maximum specific capacity of about 3,600 mAh / g (Li 15 The most widely used silicon anode materials are Si4-based. However, lithiation of silicon to its maximum capacity by intercalation of lithium into bulk silicon shows a large increase in the capacity of the silicon material, up to 400%. Repeated charge-discharge cycles impose large mechanical stresses on the silicon material, resulting in fracture and delamination of the silicon anode material. The volumetric shrinkage of silicon particles accompanying delamination can cause loss of electrical contact between the anode material and the current collector. In addition, the solid electrolyte interface (SEI) layer formed on the silicon surface does not have sufficient mechanical resistance to accommodate the expansion and contraction of silicon. As a result, newly exposed silicon surfaces lead to further electrolyte decomposition, increasing the thickness of the SEI layer and irreversible consumption of lithium. These failure mechanisms result in an unacceptable decrease in electrochemical capacity on successive charge-discharge cycles.

[0005] Many approaches have been proposed to solve the problems associated with the capacity change observed during charging of silicon-containing anodes. Small silicon structures with cross sections of 150 nm or less, such as silicon films and silicon nanoparticles, have been reported to be more resistant to capacity changes during charging and discharging than micron-sized silicon particles. However, none of these approaches are suitable for commercial-scale applications as is, as nanoscale particles are difficult to prepare and handle, and silicon films do not provide sufficient bulk capacity.

[0006] WO2007 / 083155 discloses that improved capacity retention may be obtained using silicon particles with a high aspect ratio, i.e., the ratio of the maximum dimension of the particle to the minimum dimension. The small cross section of such particles reduces the structural stress of the material due to capacity changes during charging and discharging. However, such particles may be difficult and costly to manufacture and may be fragile. Furthermore, the high surface area may result in excessive SEI formation, resulting in excessive capacity loss during the first charge-discharge cycle.

[0007] It is also commonly known that electroactive materials such as silicon can be deposited within the pores of porous carrier materials such as activated carbon materials. These composites offer some of the beneficial charge-discharge properties of nanoscale silicon particles while avoiding the difficulties of handling nanoparticles. Guo et al. (Journal of Materials Chemistry A, 2013, pp. 14075-14079) disclose a silicon-carbon composite in which a porous carbon substrate provides a conductive framework and has silicon nanoparticles deposited in a uniform distribution within the substrate's pore structure. The composite has been shown to have improved capacity retention over multiple charging cycles, but the initial capacity (mAh / g) of the composite is significantly lower than that of silicon nanoparticles.

[0008] The inventors have previously reported the development of a class of electroactive materials having a composite structure in which a nanoscale electroactive material, such as silicon, is deposited on the pore framework of a highly porous conductive particulate material, e.g. a porous carbon material.

[0009] For example, WO2020 / 095067 and WO2020 / 128495 report that the improved electrochemical performance of these materials can be attributed to the way in which the electroactive material is located in the porous material in the form of small domains with dimensions on the order of a few nanometers or less. It is believed that such fine electroactive structures have less resistance to elastic deformation and are more fracture resistant than larger electroactive structures, allowing them to be lithiated and delithiated without excessive structural stress. As a result, the electroactive material exhibits good reversible capacity retention over multiple charge-discharge cycles. Second, by controlling the loading of silicon in the porous carbon framework such that only a portion of the pore volume is occupied by silicon in an uncharged state, the unoccupied pore volume of the porous carbon framework is capable of accommodating a significant amount of silicon expansion within it. Furthermore, by locating nanoscale silicon domains within small mesopores and / or micropores as described above, only a small area of ​​the silicon surface is accessible to the electrolyte, limiting the formation of the SEI. Since further exposure of silicon during subsequent charge-discharge cycling is substantially prevented, SEI formation is not a significant failure mechanism leading to capacity loss, which is in stark contrast to the excessive SEI formation that characterizes materials disclosed, for example, by Guo (see above).

[0010] The materials described in WO2020 / 095067 and WO2020 / 128495 were synthesized by chemical vapor infiltration (CVI) in different reactor systems (static, rotating and FBR). The porous conductive particles are contacted with a flow of silicon-containing precursor (CVI), typically silane gas, in a mixture with an inert gas, at atmospheric pressure and at temperatures between 400 and 700 °C. All these reactor configurations operate in batch mode for the solid carbon scaffold and in continuous mode for the silicon precursor gas. The reaction rate of silane at this temperature is fast, but the silane molecules must follow a tortuous path across the pore system of the solid particles. This means that to obtain homogeneous infiltration in such reactor systems, the temperature must be relatively high to avoid mass transfer becoming the rate-limiting step. The result is the formation of composite products with relatively large surface areas and relatively low content of hydride-terminated silicon on average. Both of these factors are believed to lead to poor electrochemical performance.

[0011] Another drawback of systems using a continuous flow of silicon-containing precursor gas is that good mixing of the solids in the gas is required or compositional non-uniformity may occur in the product batch. Without effective mixing, solids that have a longer contact time with the gas will contain more silicon than solids that have a shorter contact time with the unreacted silane gas stream, and deposition will not be uniform across the powder bed.

[0012] Simply lowering the temperature of the CVI process cannot solve the aforementioned shortcomings: at low temperatures, mass transfer becomes the rate-limiting step, leading to poor infiltration of the porous carbon skeleton, non-homogeneous silicon distribution, and the formation of coarse silicon domains.

[0013] US 10,147,950 B2 describes the deposition of silicon from monosilane, SiH4, on porous carbon by a CVD process (chemical vapor deposition) at 300-900 °C, preferably in a tubular furnace or equivalent type of furnace with particle agitation. The process uses nitrogen as the inert gas, mixed with 2 mol % monosilane. Such conditions require very long reaction times. US 10,147,950 B2 mentions various temperature ranges and various pressure ranges.

[0014] WO2012 / 097969 A1 describes the deposition of ultrafine silicon particles in the range of 1-20 nm by heating silane as silicon precursor on a porous carbon support at 200-950 ° C, the silane being diluted with an inert gas to prevent agglomeration of the deposited silicon particles and / or the formation of a thick layer. The deposition is carried out in the pressure range of 0.1-5 bar.

[0015] Motevalian et al, Ind. Eng. Chem. Res. 2017, 56, 14995, describe the deposition of silicon layers at elevated pressures, but not in the presence of a porous matrix. Here again, the silicon precursor used, in this case monosilane, SiH4, is present only in low concentrations, up to 5 mol% in the total gas volume.

[0016] The above-mentioned process generally requires long reaction time to achieve high silicon fraction in silicon-containing composite particles.Another drawback of these processes is that only a small part of the reactive gas fed reacts, so the gas leaving the reactor must undergo expensive and inconvenient operation of recycling or disposal, which further increases costs, especially when using silicon precursor that complies with strict technical safety requirements. Summary of the Invention

[0017] Therefore, there is a need in the art for a method of producing silicon-containing composite particles, which reduces or resolves at least one of the above-mentioned shortcomings, preferably the shortcomings of high and low temperature CVI process or long reaction time.The process starting from porous particles and silicon precursor is preferably technically simple to carry out.The silicon-containing composite particles preferably have high storage capacity for lithium ions, which preferably allows high cycle stability when used as active material in the negative electrode of lithium ion battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In a first aspect, the present invention provides a method for producing silicon-containing composite particles, the method comprising the steps of: (a) providing a plurality of porous particles comprising micropores and / or mesopores, (i) D of the porous particles 50 The particle size is within the range of 0.5 to 200 μm, (ii) The total pore volume of micropores and mesopores, as measured by gas adsorption, is between 0.4 and 2.2 cm 3 / g, (iii) PD measured by gas adsorption 50 The pore size is 30 nm or less; (b) combining the charge of porous particles with a charge of silicon-containing precursor in a batch pressure reactor, wherein the charge of porous particles is mixed with the reactor volume (cm 3 / L RV ) At least 20 cm per litre 3 Preferably, the reactor volume (cm 3 / L RV ) at least 200 cm per litre 3 and the charge of silicon-containing precursor is mixed with the reactor volume (cm 3 / L RV ) containing at least 2 g of silicon per liter; (c) heating the reactor to a temperature effective to cause deposition of silicon within the pores of the porous particles, thereby providing the silicon-containing composite particles; Includes.

[0019] In a preferred embodiment of the process according to the first aspect of the present invention, said steps a) to c), in particular said steps b) to c), are carried out in the following process phases 1 to 7: Phase 1: Packing the batch pressure reactor with one or more types of porous particles; Phase 2: charging the batch pressure reactor with one or more silicon-containing precursors; Phase 3: heating the batch pressure reactor to a target temperature at which one or more silicon-containing precursors begin to decompose within the batch pressure reactor; Phase 4: Decomposing a silicon-containing precursor and depositing silicon within the pores of the porous particles and, optionally, on the surfaces of the porous particles, thereby providing the silicon-containing composite particles; Phase 5: Cooling the batch pressure reactor; Phase 6: Removing gaseous reaction products formed during deposition from the batch pressure reactor; Phase 7: Removing the silicon-containing composite particles from the batch pressure reactor; is divided into During phase 4, the pressure in the batch pressure reactor is characterized by increasing to at least 7 bar.

[0020] A method for producing silicon-containing composite particles by pyrolysis of one or more silicon-containing precursors in the presence of one or more porous particles, wherein silicon is deposited in the pores of the porous particles and, optionally, on the surfaces of the porous particles, the method comprising at least the following phases 1 to 7: Phase 1: Packing a batch pressure reactor with one or more types of porous particles, the charge of porous particles being equal to or greater than the reactor volume (cm 3 / L RV ) At least 20 cm per litre 3Preferably, the reactor volume (cm 3 / L RV ) at least 200 cm per litre 3 and the porous particles contain micropores and / or mesopores; (i) D of the porous particles 50 The particle size is within the range of 0.5 to 200 μm, (ii) The total pore volume of micropores and mesopores, as measured by gas adsorption, is between 0.4 and 2.2 cm 3 / g, (iii) PD measured by gas adsorption 50 The pore size is 30 nm or less. Phase 2: Charging the batch pressure reactor with one or more silicon-containing precursors, wherein the charge of silicon-containing precursors is greater than or equal to the reactor volume (g / L RV ) containing at least 2 g of silicon per liter; Phase 3: heating the batch pressure reactor to a target temperature at which one or more silicon-containing precursors begin to decompose within the batch pressure reactor; Phase 4: Decomposing a silicon-containing precursor and depositing silicon within the pores of the porous particles and, optionally, on the surfaces of the porous particles, thereby providing the silicon-containing composite particles; Phase 5: Cooling the batch pressure reactor; Phase 6: Removing gaseous reaction products formed during deposition from the batch pressure reactor; Phase 7: Removing the silicon-containing composite particles from the batch pressure reactor; is divided into A preferred process is wherein during phase 4 the pressure in the batch pressure reactor is increased to at least 7 bar.

[0021] In a further aspect, the present invention provides a method for producing silicon-containing composite particles by pyrolysis of one or more silicon-containing precursors in the presence of one or more porous particles, wherein silicon is deposited in the pores of the porous particles, preferably in the pores and on the surface of the porous particles, the method comprising at least the following phases 1 to 7: Phase 1: Packing the batch pressure reactor with one or more types of porous particles; Phase 2: charging the batch pressure reactor with one or more silicon-containing precursors; Phase 3: heating the batch pressure reactor to a target temperature at which one or more silicon-containing precursors begin to decompose within the batch pressure reactor; Phase 4: Decomposing a silicon-containing precursor and depositing silicon within the pores of said porous particles, preferably within the pores and on the surface of the porous particles; Phase 5: Cooling the batch pressure reactor; Phase 6: Removing gaseous reaction products formed during deposition from the batch pressure reactor; Phase 7: Removing the silicon-containing composite particles from the batch pressure reactor; Including, During phase 4, the pressure in the batch pressure reactor is characterized by increasing to at least 7 bar.

[0022] A method for producing silicon-containing composite particles by pyrolysis of one or more silicon-containing precursors in the presence of one or more porous particles is preferred, wherein silicon is deposited in the pores of said porous particles, preferably in the pores and on the surface of said porous particles, said method comprising at least the following phases 1 to 7: Phase 1: Packing a batch pressure reactor with one or more types of porous particles, the charge of porous particles being equal to or greater than the reactor volume (cm 3 / L RV ) At least 20 cm per litre 3 Preferably, the reactor volume (cm 3 / L RV ) at least 200 cm per litre 3and the porous particles contain micropores and / or mesopores; (i) D of the porous particles 50 The particle size is within the range of 0.5 to 200 μm, (ii) The total pore volume of micropores and mesopores, as measured by gas adsorption, is between 0.4 and 2.2 cm 3 / g, (iii) PD measured by gas adsorption 50 The pore size is 30 nm or less. Phase 2: Charging the batch pressure reactor with one or more silicon-containing precursors, wherein the charge of silicon-containing precursors is greater than or equal to the reactor volume (g / L RV ) containing at least 2 g of silicon per liter; Phase 3: heating the batch pressure reactor to a target temperature at which one or more silicon-containing precursors begin to decompose within the batch pressure reactor; Phase 4: Decomposing the silicon-containing precursor and depositing silicon within the pores of the porous particles, preferably within and on the pores of the porous particles; Phase 5: Cooling the batch pressure reactor; Phase 6: Removing gaseous reaction products formed during deposition from the batch pressure reactor; Phase 7: Removing the silicon-containing composite particles from the batch pressure reactor; is divided into During phase 4, the pressure in the batch pressure reactor is characterized by increasing to at least 7 bar.

[0023] For clarity only, the preferred and alternative embodiments described below refer to each of the above-mentioned aspects of the invention and each of the above-mentioned preferred processes of the invention.

[0024] The present invention therefore generally relates to a method for producing a composite particulate material, in which nanoscale silicon domains are deposited in the pore network of a porous particle, thus forming a skeleton containing the nanoscale silicon domains. As used herein, the term "nanoscale silicon domains" refers to nanoscale bodies of silicon having dimensions determined by the location of the silicon within the micropores and / or mesopores of the porous particle.

[0025] The method of the present invention is different from conventional methodologies in that the deposition of silicon is carried out in batch mode for both porous particles and silicon-containing precursor.In addition, the respective charges of porous particles and silicon-containing precursor per liter of reactor volume mean that the deposition of silicon is carried out at autogenous pressure above atmospheric pressure, and may be at least one or two orders of magnitude higher than atmospheric pressure.

[0026] The method of the present invention is also associated with many advantages, especially due to the charging of the silicon-containing precursor in the batch pressure reactor and the parameters according to the present invention. The advantageous effects can be further increased synergistically by the preferred pressure means.

[0027] First, the silicon-containing precursor can be distributed throughout the entire volume of the reactor. Thus, the reaction can be carried out at any point in the reactor, especially up to the same conversion level, unless there is a temperature profile. Inhomogeneous product composition due to contact of solids with gas streams is avoided, and materials can have the same properties regardless of their position in the reactor. The batch composition will preferably be homogeneous.

[0028] Second, the silicon-containing precursor can be distributed throughout the porous system of the porous particles before the reaction occurs. Thus, mass transfer limitations can be reduced because the silicon-containing precursor is already present in the pores at the start of the reaction. Furthermore, batch reactors can be charged with large amounts of porous particles to reduce or eliminate headspace in the reactor, such that silicon-containing precursor molecules present in the remaining reactor volume outside the pore volume of the porous particles (e.g., interstitial spaces) have a short mean free path to the nearest particle.

[0029] Third, the higher the pressure, the greater the amount of silane that can be fed to the reactor in one batch. Silane is in a supercritical state above 47.8 atmospheres and has a compressibility factor at these conditions that allows high loadings of silicon to be introduced in one batch at room temperature.

[0030] Surprisingly, the batch process allows the production of silicon-containing composite particles in a shorter reaction time and therefore in a more efficient manner. The method surprisingly allows the decomposition of an increased amount of silicon-containing precursor in particular in the porous particles and therefore an increased corresponding amount of deposited silicon in the porous particles. Moreover, the deposition of silicon is particularly uniform. This can be further improved by the preferred pressure of the present invention. This was particularly surprising since it is known from the method for producing polycrystalline silicon that the deposition of silicon at relatively high pressures is accompanied by an increased formation of unwanted dust (JOOdden et al., Solar Energy Mat. & Solar Cells 2005, 86, 165), which is counterproductive both for the deposition of silicon on the inner surface of the pores and the outer surface of the porous particles and for the yield of composite particles. This detrimental effect is surprisingly solved by the method of the present invention. These effects are particularly pronounced at the pressure in question, in particular at least 7 bar.

[0031] Fourth, the temperature is generally raised to the deposition temperature only after charging the reactor with silicon-containing precursors under pressure. This also introduces a new way to control the reaction rate and product composition. Higher silicon hydride deposition can be achieved at lower temperatures because the system does not have to deal with mass transport limitations. Thus, product composite particles with lower surface area and higher hydride-terminated silicon can be obtained compared to the atmospheric pressure synthesis route.

[0032] The method of the present invention for producing silicon-containing composite particles provides various advantages compared to the prior art.In particular, it has the advantage that it can completely convert silicon precursor in a short reaction time.These advantages are preferably further enhanced by the pressure increase in the batch pressure reactor during step (c) or phase 4, which is not caused or only caused by temperature increase.

[0033] Another advantage is that the amount of inert gas can be reduced or avoided altogether, which in turn results in a higher space / time yield and therefore a more rapid and uniform deposition of silicon in or on the porous particles.

[0034] Furthermore, it is possible to avoid the continuous recycle and treatment of reactor off-gas that typically occurs in open reactor operation.

[0035] Furthermore, by performing the process in a batch pressure reactor, multiple depositions from the same reactants, such as silicon-containing precursors, can be performed very easily with precisely adjustable amounts of deposition product based on the reactants in each deposition step.

[0036] The silicon-containing composite particles obtainable from the process of the invention are therefore preferably distinguished by an advantageous homogeneity of the deposited layer.

[0037] Moreover, a particular advantage is that the generation of dust, which is often described, can be avoided.This can be achieved, for example, by the large surface area of ​​the porous particles that is made available for the deposition of silicon from silicon-containing precursors, and by the intense penetration of the porous particles with silicon-containing precursors.At the same time, this method obtains a high yield of deposited silicon.

[0038] Furthermore, starting from porous particles and a silicon precursor, the method is technically simple to implement.

[0039] As a result of the advantages of the process of the present invention, silicon-containing composite particles are advantageously rapidly and economically available for use as the active material in the negative electrode of a lithium ion battery having particularly excellent properties.

[0040] Surprisingly, the silicon-containing composite particles produced according to the present method have a high storage capacity for lithium ions, which allows for surprisingly high cycle stability when used as an active material in the negative electrode of a lithium ion battery. The silicon-containing composite particles exhibit advantageously low volume change during cycling.

[0041] Silicon-containing composite particles can be obtained by the method of the present invention with improved properties for use in lithium-ion batteries with high volumetric energy capacity. The silicon-containing material obtained by the method of the present invention is permeable to lithium ions and also to electrons, allowing charge transport. Furthermore, the amount of decomposed electrolyte solvent and the formation of solid electrolyte interface ("SEI") can be reduced by the means of the present invention. Excessive SEI is known to have a negative impact on the cycle efficiency of lithium-ion batteries.

[0042] For the avoidance of doubt, the term "particle size" as used herein refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, where the volume of the particle is understood to include the volume of any intra-particle pores. 50 " and "D 50"Particle size" refers to the volume-based median particle size, i.e., the diameter below which 50% of the volume of the particle population is found. 10 " and "D 10 "Particle size" refers to the median particle size on a 10% volume basis, i.e., the diameter below which 10% of the volume of the particle population is found. 90 " and "D 90 "Particle size" means the median particle size on a 90% volume basis, i.e., the diameter below which 90% of the volume of the particle population is found.

[0043] Particle size and size distribution can be determined by standard laser diffraction techniques according to ISO 13320:2009. Laser diffraction relies on the principle that particles scatter light at angles that vary with particle size, and that a collection of particles produces a pattern of scattered light defined by intensity and angle that can be correlated to particle size distribution. Many laser diffraction instruments are commercially available that allow for rapid and reliable measurement of particle size distribution. Unless otherwise noted, particle size distribution measurements specified or reported herein were measured by a conventional Malvern Mastersizer® 3000 particle size analyzer from Malvern Instruments®. The Malvern Mastersizer® 3000 particle size analyzer works by projecting a helium neon gas laser beam onto a transparent cell containing particles of interest suspended in an aqueous solution. The light beam that strikes the particles is scattered at angles that are inversely proportional to the particle size, a photodetector array measures the light intensity at several predefined angles, and the intensities measured at the different angles are processed by a computer using standard theoretical principles to determine the particle size distribution. Laser diffraction values ​​reported herein are obtained using a wet dispersion of particles in 2-propanol with 5% by volume of the surfactant SPAN®-40 (sorbitan monopalmitate). The refractive index of the particles is taken to be 2.68 for porous particles and 3.50 for composite particles, with a dispersion medium index of 1.378. Particle size distributions are calculated using the Mie scattering model.

[0044] Alternatively, particle size and size distribution can be determined by static laser scattering according to ISO 13320 using the Mie model and a Horiba LA 950 instrument, preferably using ethanol as the dispersion medium for the particles.

[0045] Generally, porous particles have a D in the range of 0.5 to 200 μm. 50 Optionally, the porous particles have a D 50 The particle size may be at least 1 μm, or at least 1.5 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm. Optionally, the D of the porous particles 50 The particle size may be 150 μm or less, or 100 μm or less, or 70 μm or less, or 50 μm or less, or 40 μm or less, or 30 μm or less, or 25 μm or less, or 20 μm or less, or 18 μm or less, or 15 μm or more, or 12 μm or more, or 10 μm or less.

[0046] For example, the porous particles may have a D in the range of 0.5 to 150 μm, or 0.5 to 100 μm, or 0.5 to 50 μm, or 0.5 to 30 μm, or 1 to 25 μm, or 1 to 20 μm, or 2 to 25 μm, or 2 to 20 μm, or 2 to 18 μm, or 3 to 20 μm, or 3 to 18 μm, or 3 to 15 μm, or 4 to 18 μm, or 4 to 15 μm, or 4 to 12 μm, or 5 to 15 μm, or 5 to 12 μm, or 5 to 10 μm. 50 Particles within these size ranges and having the porosity and pore size distributions defined herein are ideally suited for the manufacture of composite particles for use in metal ion battery negative electrodes by the CVI process.

[0047] D of porous particles 10 The particle size is preferably at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10By maintaining the particle size at 0.2 μm or greater, the possibility of undesirable agglomeration of submicron-sized particles is reduced and the dispersibility of the composite particles formed is improved. 10 The particle size is preferably ≦10 μm, more preferably ≦5 μm, most preferably ≦3 μm.

[0048] D of porous particles 90 The particle size is preferably 300 μm or less, or 250 μm or less, or 200 μm or less, or 150 μm or less, or 100 μm or less, or 80 μm or less, or 60 μm or less, or 40 μm or less, or 30 μm or less, or 25 μm or less, or 20 μm or less, more preferably 18 μm or less, even more preferably 15 μm or less, and most preferably 13 μm or less. 90 The particle size is preferably 4 μm or more, and more preferably 8 μm or more.

[0049] The volume weighted particle size distribution of the porous particles is preferably determined by the diameter percentage d 10 ≧0.2μm~d 90 ≦20.0 μm, more preferably d 10 ≧0.4μm~d 90 ≦15.0 μm, and most preferably d 10 ≧0.6μm~d90≦12.0μm.

[0050] The porous particles preferably have a narrow particle size distribution range. For example, the particle size distribution range (D 90 -D 10 ) / D 50 (defined as ) is preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, more preferably 2 or less, and most preferably 1.5 or less. By keeping the particle size distribution range narrow, efficient packing of the particles into a dense powder bed is more easily achieved.

[0051] The volume-weighted particle size distribution of porous particles is d 90 Value and d 10 The difference in values ​​(D 90 -D 10The volume-weighted particle size distribution of the porous particles is preferably d ≥ 0.6 μm, more preferably ≥ 0.8 μm, most preferably ≥ 1.0 μm. 90 -d 10 It has a difference.

[0052] The porous particles are preferably present in the form of isolated particles or agglomerated particles. The porous particles are preferably not agglomerated and preferably not agglomerated. Agglomerated generally means that in the course of the production of the porous particles, primary particles are initially formed and undergo fusion and / or the primary particles bond to one another, for example via covalent bonds, thus forming aggregates. The primary particles are generally isolated particles. The aggregates or isolated particles can form agglomerates. Agglomerates are loose associations of aggregates or primary particles, which are linked to one another, for example via van der Waals interactions or hydrogen bonds. Agglomerates in agglomerates can be easily reconstituted into agglomerates by conventional kneading and dispersion techniques. The aggregates cannot be broken down into primary particles by these techniques or can only be broken down partially. The presence of the porous particles in the form of aggregates, agglomerates or isolated particles can be visualized, for example, by conventional scanning electron microscopy (SEM). Static light scattering methods for determining the particle size distribution or particle size of matrix particles, in contrast, cannot distinguish between aggregates or agglomerates.

[0053] The porous particles may have any desired morphology and thus may be, for example, plate-like, irregularly shaped, shard-shaped, spherical, or otherwise acicular, with shard-shaped or spherical particles being preferred.

[0054] The porous particles may have an average sphericity (as defined herein) of greater than 0.5. Preferably, they have an average sphericity of at least 0.55, or at least 0.6, or at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85. It is believed that the spherical particles aid in the uniformity of deposition and promote denser packing both in the batch pressure reactor and in the final product incorporated into the electrode.

[0055] Highly accurate two-dimensional projections of micron-scale particles can be obtained by scanning electron microscopy (SEM) or by dynamic image analysis using a digital camera to record the shadows cast by the particles. The term "sphericity" as used herein is to be understood as the ratio of the area of ​​the particle projection (obtained from such imaging techniques) to the area of ​​a circle, where the particle projection and the circle have the same circumference. Thus, for an individual particle, the sphericity S can be defined as:

number

number

[0056] Porous particles consist of a three-dimensionally interconnected open pore network of micropores and / or mesopores and, optionally, a small amount of macropores. In accordance with conventional IUPAC terminology, the term "micropore" is used herein to refer to pores less than 2 nm in diameter, the term "mesopore" is used herein to refer to pores between 2 and 50 nm in diameter, and the term "macropore" is used herein to refer to pores greater than 50 nm in diameter.

[0057] In this specification, references to the volume of micropores, mesopores and macropores within a porous particle, and to the distribution of pore volumes within a porous particle, relate to the internal pore volume of the porous particle used as starting material in step (a) of the defined method, i.e. prior to the deposition of silicon in the pore volume in step (c).

[0058] Porous particles are 0.4 to 2.2 cm 3 The porous particles are characterized by a total volume of micropores and mesopores in the range of 0 to 50 nm / g (i.e., a total pore volume in the range of 0 to 50 nm). Typically, the porous particles contain both micropores and mesopores. However, it is not excluded that porous particles containing micropores and no mesopores, or porous particles containing mesopores and no micropores, may be used.

[0059] More preferably, the total volume of the micropores and mesopores in the porous particles is at least 0.45 cm 3 / g, or at least 0.5 cm 3 / g, at least 0.55 cm 3 / g, or at least 0.6 cm 3 / g, or at least 0.65 cm 3 / g, or at least 0.7 cm 3 / g, or at least 0.75 cm 3 / g, or at least 0.8 cm 3 / g, at least 0.85 cm 3 / g, or at least 0.9 cm 3 / g, or at least 0.95 cm 3 / g, or at least 1 cm 3 / g. The use of high porosity particles can be advantageous as it allows a greater amount of silicon to be accommodated within the pore structure.

[0060] The internal pore volume of the porous particle is preferably upper bounded at a value where the increased fragility of the porous particle is outweighed by the benefit of increased pore volume to accommodate greater amounts of silicon. Preferably, the total volume of micropores and mesopores in the porous particle is less than 2 cm 3 / g or less, or 1.8 cm 3 / g or less, or 1.6 cm 3 / g or less, or 1.5cm 3 / g or less, or 1.45 cm 3 / g or less, or 1.4 cm 3 / g or more, or 1.35 cm 3 / g or more, or 1.3 cm 3 / g or more, or 1.25 cm 3 / g or more or 1.2cm 3 / g or more.

[0061] In some instances, the total volume of micropores and mesopores in the porous particles is between 0.45 and 2.2 cm. 3 / g, or 0.5 to 2 cm 3 / g, or 0.55 to 2 cm 3 / g, or 0.6 to 1.8 cm 3 / g, or 0.65 to 1.8 cm 3 / g, or 0.7 to 1.6 cm 3 / g, or 0.75 to 1.6 cm 3 / g, or 0.8 to 1.5 cm 3 / g.

[0062] In another example, the total volume of micropores and mesopores in the porous particle is between 0.4 and 0.75 cm 3 / g, or 0.4-0.7cm 3 / g, or 0.4 to 0.65 cm 3 / g, 0.45~0.75cm 3 / g, or 0.45 to 0.7 cm 3 / g, or 0.45 to 0.65 cm 3 / g, or 0.45 to 0.6 cm 3 / g.

[0063] In another example, the total volume of micropores and mesopores in the porous particle is between 0.6 and 2 cm. 3 / g, or 0.6 to 1.8 cm 3 / g, or 0.7-1.8cm 3 / g, or 0.7 to 1.6 cm 3 / g, or 0.8 to 1.6 cm 3 / g, or 0.8 to 1.5 cm 3 / g, or 0.8 to 1.4 cm 3 / g, or 0.9 to 1.5 cm 3 / g, or 1-1.4cm 3 / g.

[0064] PD of porous particles 50 The pore size is preferably 30 nm or less, and optionally 25 nm or less, or 20 nm or less, or 15 nm or less, or 12 nm or less, or 10 nm or less, or 8 nm or less, or 6 nm or less, or 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or more, or 2 nm or more, or 1.5 nm or less. 50 The term "pore size" refers to the volume-based median pore size based on the total volume of micropores and mesopores (i.e., the pore size below which 50% of the total volume of the micropores and mesopores reside). Thus, in accordance with the present invention, at least 50% of the total volume of the micropores and mesopores is in the form of pores having a diameter preferably less than 30 nm.

[0065] For the avoidance of doubt, any macropore volume (pore diameters greater than 50 nm) is 50 are not taken into account for purposes of determining value.

[0066] The volume ratio of micropores to mesopores in the porous particles may in principle be in the range of 100:0 to 0:100. Preferably, the volume ratio of micropores to mesopores is 90:10 to 55:45, or 90:10 to 60:40, or 85:15 to 65:35.

[0067] The pore size distribution of porous particle may be unimodal, bimodal or multimodal.As used herein, the term "pore size distribution" refers to the distribution of pore size of porous particle with respect to the cumulative total internal pore volume.It is considered that bimodal or multimodal pore size distribution is preferred because the proximity between micropores and large diameter pores provides the advantage of efficient ion transport through the porous network to silicon.

[0068] The total volume of micropores and mesopores and the pore size distribution of micropores and mesopores were determined using quenched solid-state density functional theory (QSDFT) at 77 K with a relative pressure p / p of 10, according to the standard methodology specified in ISO 15901-2 and ISO 15901-3. -6 The porosity is determined using nitrogen gas adsorption up to 1000 s or using classical adsorption models such as the Horvath-Kawazoe model for micropores according to DIN 66135 and the BJH model for mesopores according to DIN 66134. Nitrogen gas adsorption is a method to evaluate the porosity and pore size distribution of a material by condensing gas into the pores of a solid. As the pressure increases, the gas first condenses into the small diameter pores, and the pressure is increased until a saturation point is reached where all the pores are filled with liquid. The nitrogen gas pressure is then reduced in stages, allowing the liquid to evaporate out of the system. The pore volume and pore size distribution can be determined by analyzing the adsorption-desorption isotherms and the hysteresis between them. Suitable instruments for measuring the pore volume and pore size distribution by nitrogen gas adsorption include the TriStar II and TriStar II Plus porosity analyzers available from Micromeritics Instrument Corporation, USA, and the Autosorb IQ porosity analyzer available from Quantachrome Instruments.

[0069] Nitrogen gas adsorption is effective for measuring pore volume and pore size distribution for pores with diameters up to 50 nm, but is unreliable for pores with much larger diameters. Therefore, for the purposes of this invention, nitrogen adsorption is used to determine pore volume and pore size distribution only for pores with diameters up to 50 nm (i.e., only for micropores and mesopores). PD 50 is similarly determined based only on the total volume of micropores and mesopores.

[0070] Given the limitations of available analytical techniques, it is not possible to measure the pore volume and pore size distribution over the full range of micropores, mesopores, and macropores using a single technique. When a porous particle contains macropores, the volume of pores with diameters in the range of >50 nm and <100 nm can be measured by mercury porosimetry, preferably at 0.3 cm. 3 / g or less, or 0.20 cm 3 / g or less, or 0.1cm 3 / g or less, or 0.05 cm 3 / g or less. Although a small proportion of macropores are useful to facilitate electrolyte access to the pore network, the advantages of the present invention are substantially achieved by housing the silicon in the micropores and smaller mesopores.

[0071] Any pore volume measured by mercury porosimetry at pore diameters below 50 nm is disregarded (as noted above, nitrogen adsorption is used to characterize mesopores and micropores). Pore volume measured by mercury porosimetry above 100 nm is assumed to be interparticle porosity and is disregarded for purposes of this invention.

[0072] Mercury porosimetry is a technique for characterizing the porosity and pore size distribution of a material by applying various levels of pressure to a sample immersed in mercury. The pressure required for mercury to penetrate the pores of the sample is inversely proportional to the size of the pores. The values ​​obtained by mercury porosimetry reported herein were obtained according to ASTM UOP578-11, with a surface tension γ of 480 mN / m and a contact angle φ of 140° for mercury at room temperature. The density of mercury is 13.5462 g / cm at room temperature. 3 There are many high-precision mercury porosimeters on the market, such as the AutoPore IV series automated mercury porosimeter from Micromeritics, Inc., USA. For more information on mercury porosimetry, see PA Webb and C. Orr's "Analytical Methods in Fine Particle Technology, 1997, Micromeritics Instrument Corporation, ISBN 0-9656783-0."

[0073] It will be understood that intrusion techniques such as gas adsorption and mercury porosimetry are only effective for determining the pore volume of pores accessible to nitrogen or mercury from the outside of the porous particle. The porosity values ​​defined herein are understood to refer to the volume of open pores, i.e., pores accessible to fluids from the outside of the porous particle. Completely enclosed pores that cannot be identified by nitrogen adsorption or mercury porosimetry shall not be considered in determining the porosity values ​​herein. Similarly, pore volumes present in pores that are so small that they are below the detection limit by nitrogen adsorption shall not be considered.

[0074] The porous particles preferably have a diameter of ≥ 0.2 cm 3 / g, more preferably ≥ 0.6 cm 3 / g, most preferably ≥ 1.0 cm 3 / g Gurwich gas-permeable pore volume, which is useful for obtaining high-capacity lithium-ion batteries. The Gurwich gas-permeable pore volume was determined by nitrogen gas absorption measurements according to DIN66134.

[0075] The preferred porous particles are 0.3 cm 3 / g, more preferably less than 0.15 cm 3 / g. This also makes it possible to increase the capacity of the lithium ion secondary battery. The gas-impermeable pore volume can be calculated by the following formula. Pore ​​volume that cannot contain gas = 1 / density of pure material - 1 / skeletal density

[0076] The pure material density here refers to the theoretical density of a porous particle based on the phase composition, or the density of the pure material (the density of a material without closed pores). Pure material density data can be obtained by a person skilled in the art, for example, from the Ceramic Data Portal of the National Institute of Standards and Technology (NIST, https: / / srdata.nist.gov / CeramicDataPortal / scd). For example, the pure material density of carbon is 2.2 to 2.3 g / m 3 The density of the pure substance of silicon oxide is 2.203 g / cm 3 The density of the pure material of boron nitride is 2.25g / cm 3 The density of the pure silicon nitride is 3.44 g / cm 3 The density of pure silicon carbide is 3.21 g / cm 3 The skeletal density is the actual density (gas permeable) of the porous particles determined by helium pycnometry.

[0077] The porous particles are preferably based on one or more materials selected from the group consisting of hard carbon, soft carbon, mesocarbon, amorphous carbon in the form of microbeads, natural or synthetic graphite, single-walled and multi-walled carbon nanotubes and graphene; oxides such as silicon dioxide, aluminum oxide, mixed silicon-aluminum oxide, titanium oxide, magnesium oxide, lead oxide, zirconium oxide; carbides such as silicon carbide, boron carbide; nitrides such as silicon nitride, boron nitride; and other ceramic materials.

[0078] Examples of ceramic materials include those having the following formula: Al a B b C c Mg d N e O f S g where 0≦a, b, c, d, e, f, g≦1, with at least two coefficients a~g>0, and a×3+b×3+c×4+d×2+g×4≧e×3+f×2.

[0079] The ceramic material may be, for example, a binary, ternary, quaternary, pentanary, hexanary or heptanary compound. Preferred ceramic materials are those having the formula: Non-stoichiometric Boron Nitride BN z (In the formula, z=0.2~1) Nonstoichiometric carbonitrides CN z (In the formula, z=0.1~4 / 3) Boron carbonitride B x CN z (In the formula, x=0.1~20, z=0.1~20, x×3+4≧z×3) Boron Nitride Oxide BN z O r (In the formula, z=0.1~1, r=0.1~1, 3≧r×2+z×3) Boron Carbonitride Oxide B x CN z O r (In the formula, x=0.1~2, z=0.1~1, r=0.1~1, x×3+4≧r×2+z×3) Silicon carbide Si x CO z (In the formula, x=0.1~2, z=0.1~2, x×4+4≧z×2) Silicon carbonitride Si x CN z (In the formula, x=0.1~3, z=0.1~4, x×4+4≧z×3) Silicon boron carbonitride Si w B x CN z (In the formula, w=0.1~3, x=0.1~2, z=0.1~4, w×4+x×3+4≧z×3) Silicon boron carbide (Si) w Bx CO z (In the formula, w=0.10 to 3, x=0.1 to 2, z=0.1 to 4, and w×4+x×3+4≧z×2) Silicon boron oxycarbonitrideSi v B w CN x O z (In the formula, v=0.1~3, w=0.1~2, x=0.1~4, z=0.1~3, v×4+w×3+4≧x×3+z×2) Aluminum boron silicon oxycarbonitride Al u B v S x CN w O z (In the formula, u=0.1~2, v=0.1~2, w=0.1~4, x=0.1~2, z=0.1~3, u×3+v×3+x×4+4≧w×3+z×2)

[0080] An example of a porous metal oxide particle is a metal oxide particle having the formula TiO x where x has a value greater than 1 and less than 2.

[0081] Preferred porous particles are based on carbon, silicon dioxide, titanium oxide, boron nitride, silicon carbide and / or silicon nitride. More preferred materials are carbon, boron nitride and silicon dioxide.

[0082] The porous particles are more preferably porous conductive particles, and most preferably porous carbon particles.

[0083] The porous carbon particles may be based on a material selected from the group consisting of amorphous carbon, natural or synthetic graphite, carbon nanotubes, such as single-walled and multi-walled carbon nanotubes, and graphene. The amorphous carbon may be in the form of hard carbon, soft carbon, or mesocarbon microbeads. The carbon may be crystalline carbon, amorphous carbon, or a mixture of amorphous and crystalline carbon. The porous carbon particles may be either hard or soft carbon particles.

[0084] The porous carbon particles preferably comprise at least 80% by weight carbon, more preferably at least 90% by weight carbon, more preferably at least 95% by weight carbon, and optionally at least 98% or at least 99% by weight carbon.

[0085] As used herein, the term "hard carbon" generally refers to carbon atoms in nanoscale polyaromatic domains. 2 It refers to a disordered carbon matrix found predominantly in a hybridized state (triple bonds). The polyaromatic domains are generally cross-linked with chemical bonds, e.g., C-O-C bonds. Due to the chemical cross-linking between the polyaromatic domains, hard carbons cannot be converted to graphite at high temperatures. Hard carbons are characterized by a large G band (~1600 cm) in the Raman spectrum. -1 ), it generally has graphite-like properties. However, it has a large D band in the Raman spectrum (~1350 cm -1 ), carbon is generally not completely graphitic.

[0086] As used herein, the term "soft carbon" refers generally to carbon atoms split in polyaromatic domains having dimensions in the range of 5-200 nm. 2 It refers to a disordered carbon matrix found primarily in a hybridized (triple bond) state. In contrast to hard carbons, the polyaromatic domains in soft carbons are generally held together by intermolecular forces, but are not cross-linked by chemical bonds. This means that they will graphitize at high temperatures. Porous carbon particles preferably have at least 50% sp 2 For example, the porous carbon particles preferably contain 50% to 98% sp 2 Hybrid carbon, 55%-95% sp 2 Hybrid carbon, 60%-90% sp 2 Hybrid carbon, or 70%-85% sp 2 Contains hybrid carbon.

[0087] A variety of different materials can be used to fabricate a suitable porous carbon scaffold. Examples of organic materials that may be used include plant biomass, including lignocellulosic materials (coconut shells, rice husks, wood, etc.), and fossil carbon sources such as coal. Examples of resins and polymeric materials that form porous carbon particles upon pyrolysis include phenolic resins, novolac resins, pitch, melamine, polyacrylates, polystyrene, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP); various copolymers consisting of monomer units of acrylates, styrene, α-olefins, vinylpyrrolidone, and other ethylenically unsaturated monomers, etc. A variety of different carbon materials are available in the art, depending on the starting materials and the conditions of the pyrolysis process. A variety of different specifications of porous carbon particles are available from vendors.

[0088] The porous carbon particles can be subjected to a chemical or gaseous activation treatment to increase the mesopore and micropore volume. Suitable activation treatments include, for example, contacting the pyrolyzed carbon with one or more of oxygen, steam, CO, CO2 or KOH at a temperature in the range of 600-1000°C.

[0089] Porous particles are preferably open pores.Open pores generally means that pores are connected to the particle surface, for example through channels, and can preferably be in mass transfer with the surroundings, especially gaseous compounds.This can be confirmed by gas absorption measurements (evaluation according to Brunauer, Emmett, Teller, "BET"), i.e. by measuring specific surface area.

[0090] The porous particles are preferably at least 50 mm 2 / g, or at least 750m 2 / g, or at least 1,000m 2 / g, or at least 1,250m 2 / g, or at least 1,500m 2 / g. The term "BET surface area" as used herein should be taken to refer to the surface area per unit mass calculated from measurements of the physical adsorption of gas molecules on a solid surface using the Brunauer-Emmett-Teller theory in accordance with ISO 9277. Preferably, the BET specific surface area of ​​the porous particles is greater than 4,000 m 2 / g or less, or 3,500m 2 / g or less, or 3,250m 2 / g or less, or 3,000m 2 For example, the porous particles have a particle size of 750 m 2 / g~4,000m 2 / g, or 1,000m 2 / g~3,500m 2 / g, or 1,250m 2 / g~3,250m 2 / g, or 1,500m 2 / g~3,000m 2 / g.

[0091] The porous particles preferably have a density of 0.1 to 7 g / cm as determined by helium pycnometry. 3 , more preferably 0.3 to 3 g / cm 3 This is advantageous for increasing the gravimetric capacity (mAh / g) of lithium-ion batteries.

[0092] The porous particles preferably have a density of at least 0.35, preferably 3 g / cm 3 less than 2 g / cm 3 less than 1.5 g / cm 3 less than 0.35 to 1.2 g / cm 3 As used herein, the term "particle density" refers to the "apparent particle density" as measured by mercury porosimetry. (i.e., the mass of the particle divided by the volume of the particle, where the volume of the particle is considered to be the sum of the solid material and any closed or blind pores ("blind pores" are pores that are too small to be measured by mercury porosimetry).)

[0093] Preferably, the porous particles have a density of at least 0.4 g / cm 3 , or at least 0.45 g / cm 3 , or at least 0.5 g / cm 3 , or at least 0.55 g / cm 3 , or at least 0.6 g / cm 3 , or at least 0.65 g / cm 3 , or at least 0.7 g / cm 3 Preferably, the porous particles have a particle density as measured by mercury porosimetry of 1.15 g / cm 3 or less than 1.1g / cm 3 or less than 1.05g / cm 3 or less than 1g / cm 3 or less than 0.95g / cm 3 or less than 0.9g / cm 3 The particle density as measured by mercury porosimetry is

[0094] For the sake of clarity, it should be noted that porous particles are generally different from silicon-containing composite particles.Porous particles serve as the starting material for producing silicon-containing composite particles.Generally, there is preferably no silicon located in the pores of porous particles and on the surface of porous particles, more particularly the silicon obtained by depositing silicon precursor.

[0095] The silicon-containing precursor is preferably a silicon-containing liquid or gas under standard conditions (100 kPa and 20° C.). Preferably, the silicon-containing precursor is a silicon-containing gas under standard conditions.

[0096] The silicon-containing precursor generally forms silicon under thermal treatment, and is preferably selected from the group consisting of silicon-hydrogen compounds, chlorine-containing silanes and alkylsilanes.

[0097] Examples of silicon-hydrogen compounds are monosilane SiH4, disilane Si2H6, trisilane (Si3H8) and the linear, branched or cyclic higher homologues, e.g. neopentasilane Si5H 12 , Cyclohexasilane Si6H 12 Examples of chlorine-containing silanes are trichlorosilane HSiCl3, dichlorosilane H2SiCl2, chlorosilane H3SiCl, tetrachlorosilane SiCl4, hexachlorodisilane Si2Cl6 and linear, branched or cyclic higher homologues, such as 1,1,2,2-tetrachlorodisilane Cl2HSi-SiHCl2, chlorinated or partially chlorinated oligo- or polysilanes, methylchlorosilanes, such as trichloromethylsilane MeSiCl3, dichlorodimethylsilane Me2SiCl2, chlorotrimethylsilane Me3SiCl, tetramethylsilane Me4Si, dichloromethylsilane MeHSiCl2, chloromethylsilane MeH2SiCl, chlorodimethylsilane MeH2SiCl. Examples of alkylsilanes are methylsilane MeH3Si, dimethylsilane Me2H2Si, trimethylsilane Me3SiH.

[0098] More preferred silicon-containing precursors are monosilanes, SiH4; n H n+2 Linear silanes of the general formula -[SiH2] (wherein n is an integer ranging from 2 to 10); n -cyclic silanes (wherein n is an integer ranging from 3 to 10); selected from the group consisting of trichlorosilane HSiCl3, dichlorosilane H2SiCl2 and chlorosilane H3SiCl. Particularly preferred silicon-containing precursors are silane (SiH4), disilane (Si2H6), trisilane (Si3H8), methylsilane, dimethylsilane and chlorosilane. Further preferred silicon-containing precursors are selected from the group consisting of SiH4, HSiCl3 and H2SiCl2. Most preferred is silane (SiH4).

[0099] The charge of porous particles used in step (b) is preferably at least 30 cm 3 / L RV, or at least 40 cm 3 / L RV , or at least 50 cm 3 / L RV , or at least 75 cm 3 / L RV , or at least 100 cm 3 / L RV , or at least 150 cm 3 / L RV , or at least 200 cm 3 / L RV , more preferably at least 250 cm 3 / L RV , or at least 300 cm 3 / L RV , or at least 400 cm 3 / L RV , or at least 500 cm 3 / L RV , or at least 600 cm 3 / L RV , or at least 700 cm 3 / L RV , or at least 800 cm 3 / L RV , or at least 900 cm 3 / L RV Preferably, the charge of porous particles used in step (b) has a volume of at least 500 cm 3 / L RV and in some embodiments, optionally sufficient to substantially fill the reactor volume of a batch pressure reactor.

[0100] As used herein, the volume of a porous particle refers to the equivalent mass of the porous particle as determined from the tap density. For example, the volume of 200 cm of a porous particle material having a tap density of 1000 g / L as defined herein. 3 is equivalent to 200 g of porous particulate material. Tap density is measured according to ISO 3953 using 12000 taps as standard.

[0101] The charge of silicon-containing precursor used in step (b) is at least 2 g / L.RV of silicon, preferably at least 5 g / L RV of silicon, or at least 10g / L RV of silicon, or at least 15g / L RV of silicon, or at least 20g / L RV or at least 40g / L RV of silicon, or at least 60g / L RV of silicon, or at least 80g / L RV of silicon, or at least 100g / L RV of silicon, or at least 150g / L RV of silicon, or at least 200g / L RV of silicon, or at least 250g / L RV Contains silicon.

[0102] Preferably, the silicon-containing precursor used in step (b) is gas.The partial pressure of the silicon-containing precursor in the batch pressure reactor following step (b) is preferably at least 200 kPa, or at least 300 kPa, or at least 500 kPa, or more preferably at least 700 kPa, or at least 1,000 kPa, or at least 1,500 kPa, or at least 2,000 kPa, or at least 2,500 kPa, or at least 3,000 kPa, or at least 4,000 kPa, or at least 5,000 kPa.

[0103] The batch pressure reactor is preferably essentially free of oxygen gas after the porous particles and silicon-containing precursor charge are added.Oxygen can be sufficiently removed from the reactor, for example, by evacuating the reactor volume and flushing with an inert gas or with a silicon-containing precursor gas, according to standard procedures for reactions carried out in an oxygen-free atmosphere.

[0104] The batch pressure reactor may contain an inert padding gas in addition to the silicon-containing precursor, such as a noble gas such as helium, neon, argon, krypton, xenon, or nitrogen, carbon dioxide or forming gas, etc. Preferred inert gases include argon, and especially nitrogen.

[0105] The charge to the batch pressure reactor can also include hydrogen gas, particularly when the silicon-containing precursor is a chlorosilane, and preferably has an atomic ratio of hydrogen to chlorine of at least 1:1.

[0106] The batch pressure reactor may further be charged with one or more dopants. The dopants are, for example, based on compounds containing boron, nitrogen, phosphorus, arsenic, germanium, iron or nickel. The dopants are preferably selected from the group consisting of ammonia NH3, diborane B2H6, phosphane PH3, germane GeH4, arsane AsH3, and nickel tetracarbonyl Ni(CO)4. The dopants may be charged into the batch pressure reactor, for example, in step (b) or in phase 1 or phase 2 of the present invention.

[0107] The batch pressure reactor may further comprise aliphatic hydrocarbons having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, such as methane, ethane, propane, butane, pentane, isobutane, hexane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane; unsaturated hydrocarbons having 1 to 10 carbon atoms, such as ethene, acetylene, propene or butene, isoprene, butadiene, divinylbenzene, vinylacetylene, cyclohexadiene, cyclooctadiene; cyclic unsaturated hydrocarbons, such as cyclopropene, cyclobutene, cyclopentene, cyclohexene, cyclohexadiene, cyclopentadiene, dicyclopentadiene or norbornadiene; aromatic hydrocarbons, such as benzene, toluene, p-, m- or o-xylene, styrene (vinylbenzene), ethylbenzene, diphenylmethane or naphthalene; other aromatic hydrocarbons, For example, the reactor may be charged with one or more hydrocarbons selected from the group consisting of phenol, o-, m-, p-cresol, cymene, nitrobenzene, chlorobenzene, pyridine, anthracene or phenanthrene; myrcene, geraniol, thioterpineol, norbornane, borneol, isoborneol, bornane, camphor, limonene, terpinene, pinene, carane, phenol, aniline, anisole, furan, furfural, furfuryl alcohol, hydroxymethylfurfural, bishydroxymethylfuran and mixed fractions containing a plurality of these compounds, for example from natural gas condensates, crude oil distillates or coke oven condensates, mixed fractions from product streams from fluid catalytic crackers (FCC), steam crackers or Fischer-Tropsch synthesis plants, or more generally hydrocarbon-containing material streams from wood, natural gas, crude oil and coal processing. The hydrocarbons may be charged into the batch pressure reactor, for example, in step (b) or in phase 1 or phase 2 of the method of the present invention.

[0108] Following step (b), the contents of the batch pressure reactor may preferably consist essentially of the porous particles, the silicon precursor, and optionally an inert padding gas or hydrogen.

[0109] The mass ratio of the porous particles to the silicon in the silicon-containing precursor generally defines the silicon content of the composite particle product. Preferably, the mass ratio (based on silicon conversion) of the porous particles to the silicon precursor in step (b) is 95:5 to 40:60, resulting in composite particles with a theoretical silicon content of 5 to 60 wt%. For example, the mass ratio (based on silicon conversion) of the porous particles to the silicon precursor in step (b) may be at least 90:10, or at least 85:15, or at least 80:20. Optionally, the mass ratio (based on silicon conversion) of the porous particles to the silicon precursor in step (b) may be 50:50 or less, or 60:40 or less, or 70:30 or less.

[0110] The temperature in step (c) is preferably within the range of 300 to 800° C., or 300 to 750° C., or 300 to 700° C., or 300 to 650° C., or 300 to 600° C., or 320 to 550° C., or 320 to 500° C., or 340 to 450° C., or 350 to 450° C., or 300 to 395° C., or 320 to 380° C. In general, lower temperatures (e.g., 320 to 500° C., or 340 to 450° C., or 350 to 450° C., or 320 to 380° C.) are preferred because the reaction is not limited by mass transfer.

[0111] The pressure in the batch pressure reactor in step (c) is autogenous pressure, which will depend on the type of silicon-containing precursor used, as well as the size of the porous particle charge and the presence of any inert padding gas.However, in all embodiments, the pressure in step (c) is atmospheric pressure or higher, and preferably significantly higher than atmospheric pressure.For example, the pressure in step (c) can be at least 200 kPa, or at least 300 kPa, or at least 500 kPa, or preferably at least 700 kPa, or at least 1,000 kPa, or at least 1,500 kPa, or at least 2,000 kPa, or at least 2,500 kPa, or at least 3,000 kPa, or at least 4,000 kPa, or at least 5,000 kPa.Step (c) can optionally be carried out at or above the critical pressure of silicon precursor.

[0112] Deposition of silicon from silicon-containing precursors typically removes by-product gases, typically resulting in an increase in reactor pressure. For example, deposition of silicon from silane gas (SiH4) typically removes 2 moles of hydrogen gas per mole of silane gas precursor. As a result, the partial pressure of the removed hydrogen is typically significantly higher than the partial pressure of unreacted silane. In some cases, for example, when the charge of silicon-containing precursor to the reactor is small compared to the reactor volume, the pressure increase resulting from the complete conversion of the silicon-containing precursor may be within the pressure tolerance of the batch pressure reactor. The by-product gases can then simply be vented from the reactor after completion of the reaction.

[0113] In other cases, it may be necessary to control the pressure rise as the reaction proceeds, preferably so that the total pressure in the batch pressure reactor does not exceed the maximum design pressure of the batch pressure reactor. Preferably, the pressure reactor includes an integrated hydrogen-selective membrane, preferably to control the pressure rise as the reaction proceeds, and more preferably to prevent the maximum design pressure from being exceeded. This allows the by-product hydrogen gas to be separated from unreacted silane (or disilane, trisilane, etc.) so that the hydrogen gas can be vented from the reactor.

[0114] Depending on the amount of silicon deposited in step (c), the process of the present invention may be operated as a multi-pass process using successive deposition steps to deposit a target amount of silicon. The multi-pass method preferably includes the following additional steps: (d) discharging the by-product gas from the batch pressure reactor; (e) adding an additional charge of silicon-containing precursor to the batch pressure reactor, wherein the additional charge of silicon-containing precursor gas is greater than or equal to the reactor volume (g / L RV ) containing at least 2 g of silicon per liter; (f) heating the reactor to a temperature effective to cause further deposition of silicon in the pores of said porous particles; Includes.

[0115] Steps (d) through (f) can be repeated as many times as necessary to deposit the desired amount of silicon.

[0116] The preferred operating parameters for charging the silicon-containing precursor into the reactor in step (b) and reacting in step (c) described above also apply to the repetition of these steps in steps (e) and (f). Steps (e) and (f) can be carried out under the same conditions as steps (b) and (c) or under different conditions.

[0117] Optionally, at least one step (f) may be carried out at a lower temperature and / or at a lower pressure than step (c). When step (f) is repeated, each embodiment of step (f) may be carried out at a lower temperature and / or at a lower pressure than the preceding silicon deposition step (i.e., step (c) or the preceding step (f)).

[0118] It is believed that higher temperatures and higher pressures favor faster deposition rates and faster capping of the pores, resulting in lower surface areas. However, these conditions may promote silicon deposition on the outer surface of the particles, which is unfavorable for SEI formation on exposed silicon. Therefore, the ability to vary the silicon deposition rate and deposition location is a major advantage. By having multiple loading steps at different temperatures and / or pressures, the silicon deposition rate in step (c) can be increased to fill most of the pore structure, and then one or more steps (f) can be performed at lower pressures and / or temperatures to slow down the deposition rate and control the capping rate to prevent silicon deposition on the outer surface of the particles. Step (d) may optionally include a step of cooling the batch pressure reactor to a temperature below 300° C., i.e., too low for silicon deposition to occur. This allows the reactor to re-equilibrate with a new charge of silicon-containing precursor before heating back up to the reaction temperature. However, if the injection time of the new charge of silicon-containing precursor is short, the cooling step may not be necessary.

[0119] A range of different silicon loadings in the composite particles can be obtained using the methods of the present invention. For example, the amount of silicon in the composite particle product from step (c) or step (f) may suitably range from 5 to 60 wt.%, based on the total mass of silicon and porous particle framework. Preferably, the amount of silicon in the composite particle product from step (c) or step (f) is from 10 to 60% by weight, or from 15 to 60% by weight, or from 20 to 60% by weight, or from 25 to 60% by weight, or from 30 to 60% by weight, or from 35 to 60% by weight, or from 40 to 60% by weight, or from 45 to 55% by weight.

[0120] The amount of silicon in the composite particles may be selected such that, following step (c), at least 25% and up to 80% or more of the internal pore volume of the porous particles is occupied by silicon. For example, silicon may occupy 25%-60%, or 25%-55%, or 30%-50%, or 53-55%, or 40-60%, or 25%-45%, or 25%-40% of the internal pore volume of the porous particle. Within these preferred ranges, the pore volume of the porous particle is effective to accommodate the expansion of silicon during charging and discharging, but excess pore volume that does not contribute to the volumetric capacity of the particulate particle is avoided. However, the amount of silicon is also not so high as to inhibit effective lithiation due to insufficient metal ion diffusion rates or insufficient expansion volume resulting in mechanical resistance to lithiation.

[0121] The amount of silicon in the porous particles is determined by the mass ratio of silicon to the porous particles [0.5 × P 1 ~1.9×P 1 ]:1, where P1 is the total pore volume of the micropores and mesopores in the porous particle in cm 3 / g (for example, if a porous particle has a total volume of micropores and mesopores of 1.2 cm 3 / g, P 1 = 1.2). This relationship takes into account the density of silicon and the pore volume of the porous particles and defines the weight ratio of silicon at which the pore volume is approximately 20% to 82% occupied.

[0122] Preferably, at least 90% by weight, more preferably at least 95% by weight, and even more preferably at least 98% by weight of the silicon mass in the composite particles is located within the internal pore volume of the porous particles, such that there is no or very little silicon located on the external surface of the composite particles. The reaction kinetics of the CVI process ensure that preferential deposition of silicon occurs on the internal surface of the porous particles.

[0123] The composite particles can be further characterized by thermogravimetric analysis (TGA) in air. This analytical method is based on the principle that a weight gain is observed when silicon is oxidized to silicon dioxide (SiO2) at high temperatures in air. The mechanism by which silicon oxidizes is temperature dependent. Silicon atoms at the surface of silicon nanostructures oxidize at lower temperatures than silicon atoms in the bulk of the silicon nanostructure (Reference: Bardet et al., Phys. Chem. Chem. Phys. (2016), 18, 18201).

[0124] The composite particles of the present invention preferably have a low content of coarse bulk silicon, which is determined by TGA.Coarse bulk silicon is defined herein as silicon that undergoes oxidation at more than 800°C, which is determined by TGA, and where TGA is carried out in air at a temperature increase rate of 10°C / min.Therefore, the content of coarse bulk silicon is determined according to the following formula: Z = 1.875 × [(M f -M 800 ) / M f ]×100% In the formula, Z is the proportion of unoxidized silicon at 800°C, and M 800 is the mass of the sample at 800°C, and M f is the mass of ash at the end of oxidation at 1400° C. In this analysis, it is assumed that the mass increase above 800° C. corresponds to the oxidation of silicon to SiO2, and that the total mass at the completion of oxidation is SiO2.

[0125] Less preferred is silicon that undergoes oxidation above 800° C. Preferably, no more than 10% by weight of the silicon, or no more than 8% by weight of the silicon, or no more than 6% by weight of the silicon, or no more than 5% by weight of the silicon, or no more than 3% by weight of the silicon, or no more than 2% by weight of the silicon is coarse bulk silicon as determined by TGA.

[0126] The amount of silicon in the composite particles can be determined by elemental analysis.Preferably, elemental analysis can be used to determine the weight ratio of carbon (and optionally hydrogen, nitrogen and oxygen) in the porous carbon particles alone and in the silicon-containing composite particles.Determining the weight ratio of carbon in the porous carbon particles alone takes into account the possibility that the porous carbon particles contain a small amount of heteroatoms.By carrying out both measurements together, the weight ratio of silicon to the porous carbon particles can be reliably determined.

[0127] The silicon content is preferably determined by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy). Many ICP-OES instruments are commercially available, such as the iCAP® 7000 series ICP-OES analyzer available from ThermoFisher Scientific. The carbon content (as well as hydrogen, nitrogen and oxygen content, if necessary) of the composite particles and the porous carbon particles alone is preferably determined by IR absorption. A suitable instrument for measuring the carbon, hydrogen, nitrogen and oxygen content is the TruSpec® Micro elemental analyzer available from Leco Corporation.

[0128] Composite particles preferably have low total oxygen content.Oxygen may be present in composite particles, for example, as part of porous particles, or as an oxide layer on any exposed silicon surface.Preferably, the total oxygen content of composite particles is less than 15wt%, more preferably less than 10wt%, more preferably less than 5wt%, for example less than 2wt%, or less than 1wt%, or less than 0.5wt%.

[0129] The silicon-containing composite particles preferably have a D in the range of 0.5 to 30 μm. 50 The composite particles at the end of the CVI process have a particle size D 50 If the particle size is greater than 30 μm, the composite particles are preferably milled, for example by milling, to a diameter of 30 μm or less prior to use in the manufacture of an electrode. 50 The particle size is reduced to D 50Composite particles with particle sizes of 30 μm or less have good dispersibility in slurries, structural robustness, and high capacity retention over repeated charge / discharge cycles, and are suitable for forming dense electrode layers of uniform thickness in the conventional thickness range of 20 to 50 μm.

[0130] Optionally, D of the silicon-containing composite particles 50 The particle size may be at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm. 50 The particle size may be 20 μm or less, or 18 μm or less, or 16 μm or less, or 14 μm or less, or 12 μm or less, or 10 μm or less, or 8 μm or less.

[0131] For example, the silicon-containing composite particles may have a D in the range of 1 to 20 μm, or 1 to 18 μm, or 1 to 16 μm, or 2 to 16 μm, or 2 to 14 μm, or 2 to 12 μm, or 2 to 10 μm, or 2 to 8 μm. 50 It may have a particle size.

[0132] D of silicon-containing composite particles 10 The particle size is preferably 0.5 μm or more, or 0.8 μm or more, or 1 μm or more. 10 Maintaining particle size above 0.5 μm reduces the potential for undesirable agglomeration of sub-micron sized particles, resulting in improved dispersibility of the particulate material and improved volume retention.

[0133] D of silicon-containing composite particles 90 The particle size is preferably 50 μm or less, or 40 μm or less, or 30 μm or less, or 25 μm or less, or 20 μm or less, or 15 μm or less. The presence of very large particles will lead to uneven particle packing in the electrode active layer, thus disrupting the formation of a dense electrode layer, especially an electrode layer having a thickness in the range of 20 to 50 μm. Therefore, D 90 It is preferred that the particle size is at most 40 μm, more preferably even lower.

[0134] The silicon-containing composite particles preferably have a narrow particle size distribution range. For example, the particle size distribution range (D 90 -D 10 ) / D 50 (defined as) is preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, more preferably 2 or less, and most preferably 1.5 or less. By keeping the particle size distribution range narrow, efficient particle packing into a dense electrode layer is more easily achieved.

[0135] The silicon-containing composite particles are preferably 300 mm 2 / g or less, 250m 2 / g or less, 200m 2 / g or less, 150m 2 / g or less, 100m 2 / g or less, 80m 2 / g or less, 60m 2 / g or less, 40m 2 / g or less, 30m 2 / g or less, 25m 2 / g or less, 20m 2 / g or less, 15m 2 / g or more, 10m 2 / g or more, or 5m 2 The BET surface area is preferably at least 0.1 m / g. Generally, a low BET surface area is preferred to minimize the formation of a solid electrolyte interfacial (SEI) layer on the surface of the composite particles during the first charge-discharge cycle of the negative electrode. However, an excessively low BET surface area results in unacceptably low charge rates and capacities due to the inaccessibility of the bulk of the electroactive material to metal ions in the surrounding electrolyte. For example, the BET surface area is preferably at least 0.1 m 2 / g, or at least 1m 2 / g, or at least 2m 2 / g, or at least 5m 2 / g. For example, the BET specific surface area is 1 m 2 / g~25m 2 / g, more preferably 2 to 15 m 2 / g.

[0136] Preferably, the silicon-containing composite particles have a specific charge capacity at the time of initial lithiation of 1200 to 2340 mAh / g. Preferably, the silicon-containing composite particles have a specific charge capacity at the time of initial lithiation of at least 1400 mAh / g.

[0137] The reaction steps can be carried out using any reactor capable of operating in batch mode and at high pressure. Batch pressure reactors are generally batch reactors that can be operated in such a way that the pressure within the reactor is greater than the pressure surrounding the reactor.

[0138] The batch pressure reactor is preferably a type of reactor selected from the group consisting of tubular reactors, fluidized bed reactors, fixed bed reactors and autoclaves. Particularly preferred are fluidized bed reactors and autoclaves, especially autoclaves.

[0139] The porous particles and the formed composite particles may be present in the reactor in the form of a static bed of particles or in the form of a moving bed of particles. A static bed of particles is preferred when the volume of the charge of the porous particles is high relative to the available volume of the batch pressure reactor, for example at least 80%, at least 90% or at least 95% of the available volume of the batch pressure reactor (i.e., such that the reactor is substantially filled with the porous particles in step (b)). The silicon-containing precursor can then be distributed in the entire volume of the porous particles before the reaction is started. Thus, there is no mass transfer limitation since the silicon-containing precursor is already present in the pores at the start of the reaction. The reaction will proceed with the same conversion at any position in the reactor unless there is a temperature profile in the reactor.

[0140] Batch pressure reactors that can be used for stationary beds without mixing can have any desired geometric shape. Preferred forms of reactor configuration are cylindrical, conical, spherical and polyhedral or combinations thereof.

[0141] The preferred reactors for static bed reactions are shell and tube furnace type reactors. This type of reactor contains multiple reaction tubes (e.g., 10-500) arranged in a pressure vessel shell. To minimize the temperature profile during the CVI reaction, the tubes usually have a diameter of 5-200 mm. The tubes are sealed from the shell, forming two independent cavities within the reactor. The tube-side cavity constitutes the reactor volume and contains the porous particles and silicon-containing precursors during the CVI reaction. The shell-side cavity can contain a heat transfer fluid to heat or cool the contents of the tube. Alternatively, the tubes can be heated by convection or conduction using resistive heating elements.

[0142] The porous particles can be loaded into the tube, for example, by sucking through a porous plate located at one end of the tube. The tube-side cavity can then be sealed, evacuated using a vacuum, and purged with an inert gas before introducing a predetermined amount of silicon-containing precursor. The tube-side cavity can include a hydrogen-selective membrane element to facilitate removal of by-product hydrogen and control of internal pressure.

[0143] When the volume of the charge of porous particles is smaller than the reactor volume of the batch pressure reactor, the porous particles are preferably in the form of a moving bed to maintain homogeneity within the reactor.

[0144] Suitable reactors for moving bed reactions include autoclave reactors with internal agitators. The autoclave can be internally heated via multiple heating rods or tubular heat exchangers. Alternatively, the exterior wall of the autoclave can be heated by resistive heating elements or convection heating. The autoclave reactor may be equipped with a hydrogen-selective membrane element to facilitate removal of by-product hydrogen and control of internal pressure. Other methods of maintaining a moving bed of particles during the CVI reaction include vibration, ultrasound, and fluidization techniques. Suitable reactors for moving bed reactions include Parr Instrument Company® stirred pressure reactor systems, Buchi AG® Novoclave® stirred autoclaves, and others.

[0145] The moving bed batch pressure reactor can have any form of reactor configuration in which the bed of solids can be stirred, for example a moving reactor, a reactor with moving stirring elements, or a gas-passing reactor, or a combination thereof.

[0146] The form of movement in the moving bed reactor is preferably a rotational movement. Other forms of movement are suitable as well. Preferred construction forms of the rotating reactor are, for example, drum or tubular reactors, conical reactors, double cone reactors, reactors with offset cones, spherical reactors, polyhedral reactors, V-shaped reactors, double V-shaped reactors, or geometric combinations thereof. In the case of symmetrical construction forms, the axis of rotation is preferably in the axis of symmetry of the reactor. In the case of asymmetrical construction forms, the axis of rotation preferably passes through the center of gravity of the reactor. In another preferred embodiment, the axis of rotation is selected such that a tumbling movement occurs. Mixing events in the moving bed reactor are preferably promoted by internal parts. Typical internal parts are guide plates, blades, vanes, blades, etc. According to the invention, the orientation of the axis of rotation here is freely selectable. The axis of rotation is preferably oriented vertically, horizontally, or at a free angle to the horizontal embodiment.

[0147] Further preferred forms of construction of the moving bed are stationary batch pressure reactors with moving stirring elements. Preferred shapes for this are cylindrical reactors, conical reactors, spherical reactors, polyhedral reactors, or combinations thereof. The movement of the stirring elements is preferably a rotational movement. Other forms of movement are suitable as well. The stirring elements are preferably driven via a stirring shaft, and there can be one stirring element or several stirring elements per stirring shaft. Incorporated into the batch pressure reactor are preferably several stirring shafts, each of which can have one stirring element or several stirring elements. The main reactor axis is preferably aligned horizontally or vertically. In a further preferred embodiment, the stirring shaft is installed horizontally or vertically in any orientation of the reactor. In the case of a batch pressure reactor operated vertically, a preferred construction form is, for example, one in which the stirring element or several stirring elements mix the bed material by a rotational movement via the main stirring shaft. Furthermore, a construction in which two or more stirring shafts are arranged in parallel is also preferred. There are also preferred construction forms in which two or more stirring shafts are operated not parallel to each other. Another preferred form of construction for vertically operated batch pressure reactors is characterized by the use of a screw conveyor. The screw conveyor preferably conveys the bed material in the middle. A further design according to the invention is that the screw conveyor rotates along the end of the reactor. In the case of horizontally operated batch pressure reactors, a preferred construction form is, for example, one in which a stirring element or a number of stirring elements mix the bed material by a rotary movement via the main stirring shaft. Also possible is a construction in which two or more stirring shafts are arranged in parallel. Further preferred is a construction form in which two or more stirring shafts do not run parallel to each other. In the case of vertically operated batch pressure reactors, preferred stirring elements are elements selected from the group including helical stirrers, spiral stirrers, anchor stirrers or stirring elements that generally convey the bed material axially or radially or both axially and radially. In the case of horizontally operated batch pressure reactors, preferably there are several stirring elements on one shaft.The configurations according to the invention for the stirring elements of horizontally operating reactors are blades, paddles, blade stirrers, spiral stirrers or generally stirring elements which transport the bed material both axially and radially. In addition to moving stirring elements, rigid internal structures such as guide plates are also preferred in stationary batch pressure reactors with moving stirring elements. Also particularly preferred are configurations in which both the reactor and the stirring elements rotate.

[0148] As a further possibility for mixing, the material bed is preferably exposed to a gas flow. Particularly preferred here are configurations such as fluidized bed reactors. Even more preferred are batch pressure reactors, which purposely create a mixing zone in the reactor by using air pressure.

[0149] In principle, any material is suitable for the construction of the batch pressure reactor, provided that it has the necessary mechanical strength and chemical resistance under the respective conditions of use. With regard to chemical resistance, the batch pressure reactor can be made of corresponding solid materials and chemically unreactive materials (pressure-resistant materials) with specific coatings or platings on the parts in contact with the medium. These materials are preferably selected from the group including: - metallic materials: (according to DIN CEN ISO / TR 15608) steels corresponding to material groups 1 to 11, nickel and nickel alloys corresponding to groups 31 to 38, titanium and titanium alloys corresponding to groups 51 to 54, zirconium and zirconium alloys corresponding to groups 61 and 62, cast iron corresponding to groups 71 to 76; - ceramic materials including oxide ceramics, such as simple systems such as aluminum oxide, magnesium oxide, zirconium oxide, titanium dioxide (capacitor material), as well as multi-system systems such as aluminum titanate (a mixture of aluminum oxide and titanium oxide), mullite (a mixture of aluminum oxide and silicon oxide), lead zirconate titanate (piezoelectric ceramic), or dispersed ceramics such as aluminum oxide reinforced with zirconium oxide (ZTA: zirconia reinforced aluminum oxide, Al2O3 / ZrO2); non-oxide ceramics, for example carbides such as silicon carbide and boron carbide, nitrides such as silicon nitride, aluminum nitride, boron nitride and titanium nitride, borides and silicides, and mixtures thereof, and - composite materials, for example hard metals, ceramic composites, particulate composites such as concrete and polymer concrete, fibre composites such as glass fibre reinforced glass, metal matrix composites (MMC), fibre cement, carbon fibre reinforced silicon carbide, self-reinforced thermoplastics, steel reinforced concrete, fibre reinforced concrete, fibre-plastic composites such as carbon fibre reinforced plastics (CRP), glass fibre reinforced plastics (GRP), aramid fibre reinforced plastics (ARP), fibre-ceramic composites (ceramic matrix composites (CMC)), interpenetrating composites such as metal-matrix composites (MMC), dispersion reinforced aluminium alloys, dispersion reinforced nickel-chromium superalloys, layered composites such as bimetals, titanium-graphite composites, composite plates and tubes, glass fibre reinforced aluminium and sandwich structures, and structural composites.

[0150] The surface of electroactive materials deposited by CVI is generally reactive to oxygen and generally forms a native oxide layer when exposed to atmospheric oxygen. In the case of silicon, generally, an amorphous silicon oxide film is immediately formed when the silicon surface is exposed to oxygen. The formation of the native oxide layer is generally exothermic, so careful process control is required to prevent overheating and burning of particulate matter during manufacture. The presence of a native oxide layer can adversely affect the performance of the electroactive materials in lithium-ion batteries, as it is generally associated with irreversible capacity loss and reduced cycle life. Thus, the process of the present invention can optionally include a step (g) of contacting the surface of the deposited silicon with a passivating agent, where the silicon is not exposed to oxygen prior to contact with the passivating agent.

[0151] Step (g) is preferably carried out immediately after the final silicon deposition step (i.e., step (c) in the case of a single deposition step), or after the final step (f) in a multi-pass deposition process.

[0152] A passivator is defined herein as a compound capable of modifying the surface of an electroactive material so as to inhibit or prevent the formation of a surface oxide.

[0153] Suitable passivating agents include, for example, compounds that contain an alkene, alkyne or carbonyl functionality, more preferably a terminal alkene, terminal alkyne or aldehyde group.

[0154] Preferred passivating agents include one or more compounds of the following formula: (i) R-CH=CH-R (ii) RC ≡ CR (iii) O=CH-R In the above formula, R represents H or an unsubstituted or substituted aliphatic or aromatic hydrocarbyl group having 1 to 20 carbon atoms, preferably 2 to 10 carbon atoms, or the two R groups in formula (i) form an unsubstituted or substituted hydrocarbyl ring structure containing 3 to 8 carbon atoms.

[0155] Particularly preferred passivating agents include one or more compounds of the following formula: (i) CH2=CH-R (ii) HC≡CR In the above formula, R is as defined above. Preferably, R is unsubstituted.

[0156] Examples of suitable compounds include ethylene, propylene, 1-butene, butadiene, 1-pentene, 1,4-pentadiene, 1-hexene, 1-octene, styrene, divinylbenzene, acetylene, phenylacetylene, norbornene, norbordadiene, bicyclo[2.2.2]oct-2-ene. Mixtures of different passivators can also be used.

[0157] It is understood that the alkene, alkyne or carbonyl groups of the passivating agent generally undergo an insertion reaction with MH groups (wherein M represents an atom of the electroactive material) on the surface of the electroactive material to form a covalently passivated surface that is resistant to oxidation by air. When silicon is the electroactive material, the passivation reaction between the silicon surface and the passivating agent can be understood as a form of hydrosilylation, as shown diagrammatically below. [ka]

[0158] Other suitable passivation agents include compounds that contain active hydrogen atoms bonded to oxygen, nitrogen, sulfur, or phosphorus. For example, the passivation agent can be an alcohol, an amine, a thiol, or a phosphine. It is understood that the reaction of the group -XH with the hydride group on the surface of the electroactive material results in the elimination of H2, resulting in the formation of a direct bond between X and the surface of the electroactive material.

[0159] Suitable passivating agents in this category include, for example, compounds of the following formula: (iv) HX-R (wherein X represents O, S, NR or PR, and each R is independently as defined above.) The two R groups in formula (iv) may form an unsubstituted or substituted hydrocarbyl ring structure containing 3 to 8 carbon atoms. Preferably, X represents O or NH and R represents an optionally substituted aliphatic or aromatic group having 2 to 10 carbon atoms. The amine group can also be incorporated into a 4 to 10 membered aliphatic or aromatic ring structure, such as pyrrolidine, pyrrole, imidazole, piperazine, indole, or purine.

[0160] The contacting of the electroactive material with the passivating agent in step (g) may be carried out at a temperature in the range of 25 to 800° C., preferably at or below 750° C., or at or below 700° C., and at a pressure in the range of 100 kPa to 50 MPa. For example, step (g) may suitably be carried out within the preferred temperature and pressure ranges of step (c) and / or step (f) defined herein.

[0161] The passivation in step (g) may optionally be carried out in the same batch pressure reactor as steps (c) and / or (f), for example, by cooling the batch pressure reactor to an appropriate temperature, venting by-product gases from the batch pressure reactor; adding a charge of passivating agent to the batch pressure reactor; and allowing the passivating agent to passivate the exposed silicon surfaces of the composite particles.

[0162] The process of the present invention may further comprise, after the final deposition from step (c), step (f) or step (g), depositing a lithium-ion permeable material into the remaining exposed pores and / or onto the outer surface of the composite particles, thereby reducing the surface area of ​​the composite particles and sealing off the nanoscale electroactive material domains away from electrolyte access, thereby further improving the performance of the composite particles when used as an electroactive material for lithium-ion batteries.

[0163] Suitable lithium ion permeable materials include, for example, conductive pyrolytic carbon materials. Conductive pyrolytic carbon materials within the pores and / or on the outer surface of the composite particles are advantageous because they improve the electron transport to and from the bulk of the composite particles. This helps to improve the rate performance of the composite particles.

[0164] Pyrolytic carbon can be deposited on the surface of the silicon-containing composite particles by chemical vapor deposition (CVD), ie, the pyrolysis of a volatile carbon-containing gas (eg, ethylene).

[0165] A suitable process may, for example, comprise the following steps: (h) combining the composite particles from step (c), step (f) or step (g) with a pyrolytic carbon precursor; and (i) heating a pyrolytic carbon precursor to a temperature effective to cause deposition of a pyrolytic conductive carbon material within the pores and / or on the exterior surfaces of the composite particles; Includes.

[0166] Step (h) is suitably carried out at a temperature in the range of 300-800°C, or in the range of 400-700°C. For example, the temperature in step (i) may be 680°C or less, or 660°C or less, or 640°C or less, or 620°C or less, or 600°C or less, or 580°C or less, or 560°C or less, or 540°C or less, or 520°C or less, or 500°C or less. The minimum temperature in step (i) depends on the type of carbon precursor used. Preferably, the temperature in step (i) is at least 300°C, or at least 350°C, or at least 400°C, or at least 450°C, or at least 500°C. The pressure in step (i) may be in the range of 100 kPa to 50 MPa.

[0167] Suitable examples of pyrolytic carbon precursors include the hydrocarbons mentioned above.

[0168] Further examples of suitable hydrocarbons include polycyclic hydrocarbons containing 10-25 carbon atoms and optionally 1-3 heteroatoms, optionally selected from naphthalene, substituted naphthalenes such as dihydroxynaphthalene, anthracene, tetracene, pentacene, fluorene, acenaptene, phenanthrene, fluoroanthrene, pyrene, chrysene, perylene, coronene, fluorenone, anthraquinone, anthrone, and alkyl-substituted derivatives thereof. Suitable pyrolytic carbon precursors include bicyclic monoterpenoids, optionally selected from camphor, borneol, eucalyptol, camphene, carene, sabinene, thujene, and pinene. Further suitable pyrolytic carbon precursors include C2-C10 hydrocarbons, optionally selected from alkanes, alkenes, alkynes, cycloalkanes, cycloalkenes and arenes, such as methane, ethylene, propylene, limonene, styrene, cyclohexene, α-terpinene and acetylene. Other suitable pyrolytic carbon precursors include phthalocyanine, sucrose, starch, graphene oxide, reduced graphene oxide, pyrenes, perhydropyrene, triphenylene, tetracene, benzopyrene, perylenes, coronene and chrysene. A preferred carbon precursor is acetylene.

[0169] The pyrolytic carbon precursor used in step (i) may be used in a pure state or may be diluted and mixed with an inert carrier gas such as nitrogen or argon. For example, the pyrolytic carbon precursor may be used in an amount ranging from 0.1 to 100% by volume, or from 0.5 to 20% by volume, or from 1 to 10% by volume, or from 1 to 5% by volume, based on the total volume of the precursor and the inert carrier gas. The presence of oxygen should again be minimized to prevent undesired oxidation of the deposited electroactive material. Preferably, the oxygen content is less than 0.01% by volume, more preferably less than 0.001% by volume, based on the total volume of the gas used in step (i).

[0170] Deposition of the conductive carbon by CVD may optionally be carried out in the same batch pressure reactor as step (c) and / or step (f), for example, by cooling the batch pressure reactor to an appropriate temperature, venting by-product gases from the batch pressure reactor, adding a charge of carbon-containing precursor to the batch pressure reactor, and heating the reactor to a temperature effective to cause deposition of the pyrolyzed conductive carbon material within the pores and / or on the exterior surfaces of the composite particles.

[0171] Alternatively, deposition of conductive carbon by CVD may be carried out in another conventional reactor type (e.g., a fluidized bed reactor, or a rotary kiln reactor) under a flow of gas containing a carbon-containing precursor. Alternatively, the carbon coating may be formed by depositing a solution of a carbon-containing compound on the surface of the composite particles, followed by pyrolysis.

[0172] The carbon coating has the advantage of smoothing out surface defects and filling remaining surface micropores, thereby further reducing the BET surface area of ​​the composite particles, thereby further reducing first cycle losses. Additionally, the carbon coating improves the electrical conductivity of the composite particle's surface, reducing the need for conductive additives in the electrode composition, and also creates an optimal surface for the formation of a stable SEI layer, thereby improving capacity retention upon cycling.

[0173] In addition, the reduction in the surface area of ​​the composite particles also has the effect of reducing the amount of binder required to form an electrode active layer containing the composite particles, since excessive binder is known to be a cause of reduced rate performance.

[0174] When a carbon coating is present, the silicon-containing composite particles are preferably 2 / g or less, or 100m 2 / g or less, or 80m 2 / g or less, or 60m 2 / g or less, or 40m 2 / g or less, or 30m 2 / g or less, or 25m 2 / g or less, or 20m 2 / g or less, or 15m 2 / g or less, or 10m 2 / g or less, 5m 2 / g or less, or 3m 2 / g or less BET surface area.

[0175] When the lithium ion permeable filler material is a conductive pyrolytic carbon material, the same compound may function as both the passivator in step (g) and the pyrolytic carbon precursor in step (h). For example, if styrene is selected as the pyrolytic carbon precursor, styrene also functions as the passivator, provided that the silicon is not exposed to oxygen before contacting with the styrene. In this case, the passivation in step (g) and the deposition of the conductive carbon material in steps (h) and (i) can be carried out simultaneously, for example, at a temperature in the range of 300 to 800°C. Alternatively, the passivation in step (g) and the deposition of the conductive carbon material in steps (h) and (i) can be carried out sequentially using the same materials as the passivator and pyrolytic carbon precursor, but step (i) is carried out at a higher temperature than step (g). For example, step (g) may be carried out at a temperature in the range of 25°C to less than 300°C, and step (i) may be carried out at a temperature in the range of 300 to 800°C.

[0176] Alternatively, different compounds may be used as the passivation agent in step (g) and the pyrolytic carbon precursor in step (h). For example, the electroactive material may first be contacted with a passivation agent in step (g), and then the conductive pyrolytic carbon material may be deposited in steps (h) and (i), where the pyrolytic carbon precursor used in step (h) is different from the passivation agent used in step (g). For example, the passivation agent in step (g) may be styrene, and the pyrolytic carbon precursor in step (h) may be a compound such as cyclohexane that can form a pyrolytic carbon material but cannot passivate the electroactive material surface.

[0177] In the following, some preferred embodiments of phases 1 to 7 of the present process are described in more detail. For clarity, the above-mentioned general or preferred embodiments of the present process, such as starting materials such as porous particles, silicon-containing precursors, dopants or hydrocarbons, or reaction conditions such as temperature, pressure or inert gas padding, or batch pressure reactor embodiments or process execution, are disclosed in conjunction with the following description of phases 1 to 7 with reference to the following phases 1 to 7.

[0178] In phase 1, the porous particles are loaded into a batch pressure reactor, which is then typically closed.

[0179] The filling of the porous particles into the batch pressure reactor can be carried out, for example, under an inert gas atmosphere or preferably under ambient air.The inert gas can be selected from the group consisting of hydrogen; noble gases, such as helium, neon, argon, krypton, xenon; nitrogen; carbon dioxide or forming gas or mixtures thereof.Argon or, in particular, nitrogen is preferred.

[0180] In phase 2, one or more silicon-containing precursors are charged to a batch pressure reactor.

[0181] In phase 2, it is particularly preferred to firstly charge the batch pressure reactor with inert gas or evacuate and evacuate the batch pressure reactor, especially before charging the batch pressure reactor with silicon-containing precursor.Examples and preferred embodiments of inert gas are described above for phase 1. It is particularly preferred to operate without inert gas.

[0182] The batch pressure reactor is preferably charged with an amount of silicon-containing precursor such that a sufficient amount of silicon is deposited in the target volume of the silicon-containing composite particles to be produced, relative to the weighted amount of porous particles.

[0183] In this context, loading generally means the introduction of silicon-containing precursor into batch pressure reactor.When being introduced into batch pressure reactor, silicon-containing precursor can be present in the form of, for example, gas, liquid or sublimable solid.Then, batch pressure reactor is generally closed gas-tightly.

[0184] The batch pressure reactor is charged in phase 2 with one or more silicon-containing precursors and optionally one or more further components such as one or more inert gases, hydrogen, one or more dopants or one or more hydrocarbons. The silicon-containing precursors can generally be introduced into the batch pressure reactor as a mixture or separately, or as a mixture with an inert gas or as a pure substance. The partial pressure of the inert gas is preferably 0 to 99%, more preferably at most 50%, particularly preferably at most 30%, and very particularly preferably at most 5%, based on the total pressure of the silicon-containing precursor under standard conditions (according to DIN 1343). In a particularly preferred embodiment, the batch pressure reactor does not contain an inert gas. The embodiment of such a dopant or such a hydrocarbon has been described above.

[0185] In phase 3, in other words, after the silicon-containing precursor is generally charged into the batch pressure reactor, the batch pressure reactor, which is generally closed, is heated until a target temperature is reached. At the target temperature, the decomposition of the silicon-containing precursor begins, resulting in the deposition of silicon in the pores of the porous particles and optionally on the surface. The onset of the decomposition of the silicon-containing precursor with the deposition of silicon can be experimentally confirmed by an increase in pressure in the batch pressure reactor, which is not brought about by an increase in temperature in the batch pressure reactor. In the case of the decomposition of the silicon-containing precursor, gas molecules are generally formed as well as silicon, which results in an increase in pressure in the batch pressure reactor. The volume of the batch pressure reactor is generally kept constant during the implementation of the process. The decomposition temperature is also listed in standard chemical tables of chemical properties.

[0186] Preferably, in phase 3, the pressure change during heating of the closed batch pressure reactor is, for example, as shown in the following formula 1:

number

[0187] After attainment of the target temperature for the decomposition of the silicon-containing precursor in phase 3, the temperature of phase 4 in the batch pressure reactor can be, for example, increased, constant, or decreased to a small extent relative to the target temperature of phase 3.

[0188] Temperature, pressure, or differential pressure measurements in the Phase 3 batch pressure reactor can be determined using measurement techniques and equipment common to batch pressure reactors. Following routine calibration, different measurement equipment will give the same results.

[0189] The target temperature is preferably located in the range of 370-1000°C, more preferably 390-800°C, and most preferably 400-550°C. In the case of SiH4, for example, the target temperature is preferably in the range of 370-500°C, more preferably 390-450°C, and very preferably 400-420°C. The target temperature of HSiCl3 is preferably in the range of 400-1000°C, more preferably 600-800°C. The target temperature of H2SiCl2 is preferably in the range of 350-800°C, more preferably 450-550°C.

[0190] If a hydrocarbon is charged, the target temperature applied at the end of phase 3 and during phase 4 is preferably the temperature at which decomposition of the hydrocarbon begins and carbon deposits in the pores of the porous particles and optionally on the surface. In this embodiment, the selected target temperature is preferably in the range of 250-1000°C, more preferably 350-850°C, most preferably 450-650°C.

[0191] The pressure in the batch pressure reactor during phase 4 is preferably increased to at least 7 bar.

[0192] In a preferred embodiment, the progress of reaction during the process is monitored based on pressure change.In this way, it is possible to ascertain, for example, the degree of infiltration or the end of infiltration.Infiltration means the deposition of silicon in the pores of the porous particles of phase 4 and optionally on the surface.The end of infiltration can be determined, for example, by the absence of further pressure increase.

[0193] The pressure change in the batch pressure reactor during phase 4 is generally, for example, according to Equation 2:

number

[0194] The pressure change in phase 4 is preferably a substantial product of the change in the amount of material during the deposition of silicon.Therefore, advantageously, the end of the reaction of the silicon-containing precursor can be recognized from the absence of further pressure increase at the end of phase 4, so that further phases can be effectively triggered in time to achieve full conversion without unnecessarily removing unreacted silicon-containing precursor from the reactor.

[0195] In phase 4, the temperature is preferably not increased by heating. The temperature in phase 4 is preferably increased as a result of the heat resulting from the possibly exothermic decomposition of the silicon-containing precursor. More preferred is a slight temperature decrease in phase 4, more preferably a temperature decrease of up to 20° C. during phase 4.

[0196] The pressure increase in the batch pressure reactor in phase 4 (decomposition of the silicon-containing precursor) is preferably higher than that in phase 3 (heating of the batch pressure reactor), which can be, for example, represented by the following formula 3a:

number

number

[0197] The pressure in the batch pressure reactor in phase 4 preferably reaches at least 10 bar, more preferably at least 50 bar, more preferably at least 100 bar. The pressure in the batch pressure reactor in phase 4 preferably remains at or below 400 bar, more preferably at or below 300 bar, particularly preferably at or below 200 bar.

[0198] The temperature prevailing in the batch pressure reactor of phase 4 is preferably in the range of 100-1000°C, more preferably in the range of 300-900°C, most preferably in the range of 380-750°C.

[0199] Temperature, pressure, pressure change or differential pressure measurements in the batch pressure reactor of Phase 4 can be determined using techniques and equipment common to batch pressure reactors. Different measurement equipment will give the same results if routine calibration is followed. The amount of material or change in the amount of material can be determined by, for example, removing a defined volume sample from the batch pressure reactor and determining its net composition in a conventional manner by gas chromatography.

[0200] Heating of the batch pressure reactor in phase 3 and optionally in phase 4 may be carried out, for example, at a constant heating rate or at several different heating rates. The heating rate can be adapted by a person skilled in the art in each individual case according to the design of the process, for example, according to the size of the reactor, the amount of porous particles in the reactor, the stirring technique, or the planned reaction time. The entire batch pressure reactor is preferably heated in phase 3 at such a rate that, despite the rapid heating, the maximum temperature gradient in the batch pressure reactor at the temperature at which the decomposition of the silicon-containing precursor begins remains less than 1000 ° C. / m, more preferably less than 100 ° C. / m, and very preferably less than 10 ° C. / m. In this way, for example, it is possible to ensure that most of the silicon is deposited in the pores of the porous particles and not on their outer surface.

[0201] The temperature at which the decomposition of the silicon-containing precursor begins may depend, for example, on the porous particles used or the silicon-containing precursor used, and other boundary conditions of the decomposition, such as the partial pressure of the silicon-containing precursor at the moment of decomposition, and the presence of other reactive components that affect the decomposition reaction, such as catalysts.

[0202] Heating of the batch pressure reactor in phase 3 is preferably carried out at a heating rate of 1-100° C. / min, more preferably at a heating rate of 2-50° C. / min, and very preferably at a heating rate of 3-10° C. / min.

[0203] During the decomposition of the silicon-containing precursor in phase 4, the temperature can be kept constant or can be varied. The objective is to achieve near complete conversion of the silicon-containing precursor in as short a time as possible to produce a usable silicon-containing material.

[0204] To control the rate of pressure rise in the various phases of operation, there are various technical solutions available. To increase or decrease the pressure rise, the heat supplied to the reactor contents is preferably increased or decreased, respectively. To decrease the rate of pressure rise, it is also preferred to increase the removal of heat by cooling from the batch pressure reactor. For this purpose, preferably one or more reactor walls are cooled or equipment for removing heat is introduced into the reactor, examples being cooling pipes or cooling ribs. To control the pressure in the reactor very quickly, it is preferred to feed or remove small amounts of gas from the batch pressure reactor or to feed an evaporating liquid. In this context, the side stream removed from the batch pressure reactor is returned again in whole or in part to the reactor contents, preferably in a closed circuit, after cooling and / or removal of part of the total stream.

[0205] The progress of the reaction in phase 4 is preferably monitored analytically in order to recognize the end of the reaction and thus minimize the reactor occupancy time. Methods for observing the progress of the reaction include, for example, temperature measurements to determine exothermic or endothermic phenomena, pressure measurements to determine the progress of the reaction through changes in the ratio of the solid and gaseous reactor content components, as well as further techniques that allow the observation of the changing composition of the gas space during the reaction.

[0206] It is preferred to monitor the pressure change in the batch pressure reactor during the process, particularly the pressure increase, which is an indication of the deposition rate and therefore the remaining surface area of ​​the porous particles and / or the resulting silicon-containing material.

[0207] In phase 5, the batch pressure reactor is cooled. Cooling preferably occurs after deposition is completed, optionally to below the target temperature, preferably to the temperature of phase 6.

[0208] In phase 6, the gaseous by-products of the reaction formed in the course of the deposition are removed, preferably at the temperature of the deposition or after attainment of the temperature desired for the removal of the gaseous reaction by-products, from the gas space of the batch pressure reactor, for example by purging. It is preferable to use a purge gas. Before the purge gas is charged, the batch pressure reactor is preferably evacuated at least once. Preferred purge gases are inert gases, for example noble gases such as helium, neon, argon, krypton, xenon, or hydrogen or nitrogen or carbon dioxide, which can be used individually or as mixtures or mixtures thereof with oxygen, for example air or rare air.

[0209] The batch pressure reactor is preferably purged with a mixture of inert gas and oxygen. In this way, for example, it is possible to modify, for example inactivate, the surface of the silicon-containing composite particles. For example, it is possible to achieve reaction of any reactive groups present on the surface of the silicon-containing composite particles. The mixture of nitrogen and oxygen preferably contains oxygen at most 20% by volume, more preferably at most 10% by volume, and particularly preferably at most 5% by volume. This process is preferably carried out at a temperature of at most 200°C, more preferably at most 100°C, and particularly preferably at most 50°C.

[0210] In phase 7 of the process, the silicon-containing composite particles are removed from the batch pressure reactor, optionally while retaining the inert gas atmosphere present in the batch pressure reactor.

[0211] In one preferred embodiment of the process, phases 2 through 6 are repeated multiple times, where the silicon-containing precursor charged in phase 2 can be the same or different in each case.

[0212] In a further preferred embodiment of the process, phase 6 follows directly on phase 4, in other words phase 5 can be omitted, in other words it is also possible to continue with phase 6 after phase 4 without cooling the batch pressure reactor.

[0213] In a further preferred embodiment of the process, phases 2 through 6 are repeated one or more times, optionally omitting phase 6 in one or more repetitions.

[0214] In a further preferred embodiment, phases 2 to 6, optionally omitting phase 5, are repeated one or more times (reaction cycles), in which case it is also possible to employ a silicon-free reactive component in one or more repetitions, in which case the silicon-free reactive components in each repetition may be the same or different, provided that at least one reaction cycle uses a reactive component that contains a silicon-containing precursor. The silicon-free reactive component preferably does not contain a silicon-containing precursor. The silicon-free reactive component preferably contains one or more hydrocarbons. In this preferred embodiment, a silicon-free reactive component can be used in the repetitions of phases 2 to 6. A preferred silicon-free reactive component is a hydrocarbon. When using a silicon-free reactive component, carbon is preferably deposited in the pores and optionally on the surface of the porous particles or silicon-containing composite particles.

[0215] In a particularly preferred embodiment, in the first reaction cycle, in phase 2, one or more silicon-containing precursors are charged, and in the second reaction cycle, one or more reactive components comprising hydrocarbons are charged, this latter component preferably not comprising silicon-containing precursors, and phase 5 is optionally omitted. By this means, for example, it is possible to obtain silicon-containing composite particles that do not have free silicon surfaces facing outward.

[0216] In a further preferred embodiment, in the first reaction cycle, in phase 2, a reactive component containing at least one hydrocarbon and not containing a silicon-containing precursor is charged, and in the second reaction cycle, a reactive component containing one or more silicon-containing precursors is used, and phase 5 is optionally omitted. Optionally, in the third reaction cycle, a further hydrocarbon-containing reactive component not containing a silicon-containing precursor is used, and phase 5 is optionally omitted. The result is, for example, a silicon-containing composite particle having a carbon layer between the porous particle and the deposited silicon, and optionally further having an outer carbon layer, which means that there is no free silicon surface facing outward. A preferred reactive component different from the silicon-containing precursor is one or more hydrocarbons. The hydrocarbons and their preferred embodiments are as described above.

[0217] The reactive components that include one or more hydrocarbons but do not include a silicon-containing precursor preferably do not include additional components or do not include one or more inert gases and / or hydrogen and / or one or more dopants, the dopants and their preferred embodiments being described above.

[0218] During phases 2 to 6, the porous particles and also the resulting silicon-containing composite particles may generally be in the form of a stationary bed or in the form of an agitated bed with mixing. Agitated mixing of the porous particles and / or the resulting silicon-containing composite particles in a batch pressure reactor is preferred. It allows, for example, homogeneous contact of all the porous particles with the reactive components, especially the silicon-containing precursor, or homogeneous temperature distribution in the bed. The particles can be agitated, for example, by agitated internal parts in the reactor, by the movement of the entire reactor, or by fluidizing the solids in the reactor with a gas flow.

[0219] Steps a) to c) of the present method are preferably divided into the above-mentioned process phases 1 to 7, more preferably steps b) to c) are divided into process phases 1 to 7. Step b) preferably consists of phases 1 and 2. Step c) preferably consists of phases 3 to 7, in particular phases 3 and 4.

[0220] The silicon-containing composite particles obtainable by the process of the present invention preferably have a diameter fraction d in the range of 0.5 to 20 μm. 50 d 50 The value is preferably at least 1.5 μm, more preferably at least 2 μm. 50 is preferably at most 13 μm, more preferably at most 8 μm.

[0221] The volume-weighted particle size distribution of the silicon-containing composite particles is preferably a diameter fraction d 10 ≧0.2μm and d 90 ≦20.0 μm, more preferably d 10 ≧0.4μm and d 90 ≦15.0 μm, most preferably d 10 ≧0.6μm and d 90 Between ≦12.0 μm.

[0222] The silicon-containing composite particles have a diameter ratio d 10 preferably has a volume-weighted particle size distribution of ≦10 μm, more preferably ≦5 μm, particularly preferably ≦3 μm, and most preferably ≦1 μm. 10 is preferably ≧0.2 μm, more preferably ≧0.4 μm, and most preferably ≧0.6 μm.

[0223] The silicon-containing composite particles have a diameter ratio d 90 preferably has a volume-weighted particle size distribution of ≧5 μm, more preferably ≧10 μm. 90 is preferably ≦20 μm, more preferably ≦15 μm, and most preferably ≦12 μm.

[0224] The volume-weighted particle size distribution of the silicon-containing composite particles is preferably ≦15.0 μm, more preferably ≦12.0 μm, even more preferably ≦10.0 μm, particularly preferably ≦8.0 μm, and most preferably ≦4.0 μm. 90 -d 10 The volume-weighted particle size distribution of the silicon-containing composite particles preferably has a d 90 -d 10 It has a difference.

[0225] Silicon-containing composite particles may be isolated or agglomerated.Silicon-containing composite particles are preferably not agglomerated, and preferably not agglomerated.The terms isolated, agglomerated and non-agglomerated have already been defined above in relation to porous particles.The presence of silicon-containing composite particles in the form of agglomerates or agglomerates can be visualized, for example, by conventional scanning electron microscope (SEM).

[0226] The silicon-containing composite particles may have any desired morphology and thus may be, for example, plate-like, irregularly shaped, shard-shaped, spherical, or otherwise acicular, with shard-shaped or spherical particles being preferred.

[0227] According to Wadell's definition, sphericity ψ is the ratio of the surface area of ​​a sphere of equal volume to the actual surface area of ​​the object. For a sphere, the value of ψ is 1. According to this definition, the silicon-containing composite particles obtainable by the process of the present invention preferably have a sphericity ψ of 0.3 to 1.0, more preferably 0.5 to 1.0, and most preferably 0.65 to 1.0.

[0228] Sphericity S is the ratio of the circumference of an equivalent circle having the same area A as the projection of the particle onto the surface to the measured circumference U of this projection:

number

[0229] The cycling stability of lithium-ion batteries can be further enhanced through the morphology, material composition, particularly the specific surface area or internal porosity of the silicon-containing composite particles.

[0230] The silicon-containing composite particles preferably contain 10 to 90% by weight, more preferably 20 to 80% by weight, very preferably 30 to 60% by weight, and particularly preferably 40 to 50% by weight of porous particles, based on the total weight of the silicon-containing composite particles.

[0231] The silicon-containing composite particles preferably contain 10 to 90% by weight, more preferably 20 to 80% by weight, very preferably 30 to 60% by weight, and particularly preferably 40 to 50% by weight of silicon obtained by deposition from a silicon-containing precursor, based on the total weight of the silicon-containing composite particles (preferably determined by elemental analysis such as ICP-OES).

[0232] When the porous particles contain a silicon compound, such as silicon dioxide, the weight percent of silicon obtained via deposition from a silicon-containing precursor can be determined by subtracting the mass of silicon in the porous particles as determined by elemental analysis from the mass of silicon in the silicon-containing composite particles as determined by elemental analysis, and dividing the result by the mass of the silicon-containing composite particles.

[0233] The volume of silicon contained in the silicon-containing composite particles and obtained through deposition from a silicon-containing precursor is calculated by multiplying the mass fraction of silicon obtained through deposition from a silicon-containing precursor to the total mass of the silicon-containing composite particles by the density of silicon (2.336 g / cm 3 ) is the value divided by

[0234] The pore volume P of the silicon-containing composite particles is the sum of the gas-permeable pore volume and the gas-impermeable pore volume. The Gurwich gas-permeable pore volume of the silicon-containing composite particles can be determined by nitrogen gas adsorption measurement according to DIN66134.

[0235] The gas infiltrating pore volume of the silicon-containing composite particles is calculated by the following formula: Pore ​​volume that can enter gas = (1 / density of pure material) - (1 / skeletal density) It can be determined by:

[0236] Here, the pure material density of the silicon-containing composite particles is a theoretical density that can be calculated by multiplying the theoretical pure material density of the components contained in the silicon-containing composite particles by their weight-based fractions in the entire material. Therefore, for example, in the case of silicon-containing composite particles in which silicon is deposited on porous particles, it is as follows. Pure material density = (theoretical pure material density of silicon x fraction of silicon (wt%)) + (theoretical pure material density of porous particles x fraction of porous particles (wt%))

[0237] Pure material density data can be obtained by those skilled in the art, for example, from the Ceramic Data Portal of the National Institute of Standards and Technology (NIST, https: / / srdata.nist.gov / CeramicDataPortal / scd). For example, the pure material density of carbon is 2.2 to 2.3 g / m 3 The density of the pure substance of silicon oxide is 2.203 g / cm 3 The density of the pure material of boron nitride is 2.25 gcm 3 The density of the pure silicon nitride is 3.44 g / cm 3 , and the density of the pure material of silicon carbide is 3.21 g / cm 3 It is.

[0238] The pore volume P of the silicon-containing composite particle is preferably within a range of 0 to 400 volume %, more preferably within a range of 100 to 350 volume %, and even more preferably within a range of 200 to 350 volume %, based on the volume of silicon contained in the silicon-containing composite particle and obtained by deposition of the silicon-containing precursor.

[0239] The pores contained in the silicon-containing composite particles may be both gas-permeable and gas-impermeable. The ratio of the volume of the gas-permeable pores of the silicon-containing composite particles to the volume of the gas-impermeable pores is generally within the range of 0 (no gas-permeable pores) to 1 (all pores are gas-permeable). The ratio of the volume of the gas-permeable pores of the silicon-containing composite particles to the volume of the gas-impermeable pores is preferably within the range of 0 to 0.8, more preferably within the range of 0 to 0.3, and particularly preferably within the range of 0 to 0.1.

[0240] The pores of the silicon-containing composite particles may have any desired diameter, for example located in the range of macropores (>50 nm), mesopores (2-50 nm) and micropores (<2 nm). The silicon-containing composite particles may also contain any desired mixture of different pore types. The silicon-containing composite particles preferably contain up to 30% macropores based on the total pore volume, silicon-containing composite particles without macropores are particularly preferred, and silicon-containing composite particles having at least 50% pores with an average pore diameter of less than 5 nm based on the total pore volume are very particularly preferred. It is particularly preferred that the silicon-containing composite particles exclusively have pores with a diameter of up to 2 nm.

[0241] The silicon-containing composite particles comprise silicon structures having a structure size in at least one dimension preferably up to 1000 nm, more preferably less than 100 nm, and very preferably less than 5 nm (determination method: scanning electron microscope (SEM) and / or high resolution transmission electron microscope (HR-TEM)).

[0242] The silicon-containing composite particles preferably comprise a silicon layer having a layer thickness of less than 1000 nm, more preferably less than 100 nm, and very preferably less than 5 nm (determination method: scanning electron microscope (SEM) and / or high-resolution transmission electron microscope (HR-TEM)). The silicon-containing composite particles may also comprise silicon in the form of particles. The silicon particles preferably have a diameter of at most 1000 nm, more preferably less than 100 nm, and very preferably less than 5 nm (determination method: scanning electron microscope (SEM) and / or high-resolution transmission electron microscope (HR-TEM)). Note that the numerical value of the silicon particles here is preferably based on the diameter of the circle around the particle in the microscopic image.

[0243] Silicon-containing composite particles can be up to 50m 2 / g, preferably 30m 2 / g, particularly preferably less than 10m 2 The silicon-containing composite particles have a specific surface area of ​​less than 100 nm / g. The BET specific surface area is determined according to DIN 66131 (using nitrogen). Therefore, when the silicon-containing composite particles are used as an active material for a negative electrode of a lithium ion secondary battery, the generation of SEI can be suppressed and the initial coulombic efficiency can be improved.

[0244] The silicon in the silicon-containing composite particles deposited from the silicon-containing precursor may further comprise one or more dopants selected from the group consisting of Li, Fe, Al, Cu, Ca, K, Na, S, Cl, Zr, Ti, Pt, Ni, Cr, Sn, Mg, Ag, Co, Zn, B, P, Sb, Pb, Ge, Bi and rare earths. Here, lithium and / or tin are preferred. The amount of dopant in the silicon-containing composite particles is preferably at most 1 wt.%, more preferably at most 100 ppm, based on the total weight of the silicon-containing composite particles, which can be determined by means of ICP-OES.

[0245] Silicon-containing composite particles generally have surprisingly high stability under compression and / or shear load.The pressure stability and shear stability of silicon-containing composite particles are shown, for example, by the absence or practical absence of change in the porous structure of silicon-containing composite particles under compression load (e.g., during electrode molding) and shear load (e.g., during electrode preparation) in SEM.

[0246] The silicon-containing composite particles may optionally further comprise elements such as carbon. The carbon is preferably present in the form of thin layers with a layer thickness of at most 1 μm, preferably less than 100 nm, more preferably less than 5 nm, very preferably less than 1 nm (determinable via SEM or HR-TEM). These carbon layers may be present both in the pores and on the surface of the silicon-containing composite particles. The order of the different layers in the silicon-containing composite particles with the corresponding repetition of phases 2 to 6, as well as their number, is also arbitrary. Thus, firstly, on the porous particles there is a layer of a further material different from the porous particles, such as carbon, which layer may bear a silicon layer or a layer of silicon particles. It is also possible that on the silicon layer or layer of silicon particles there is a layer of a further material, which may be different or the same as the material of the porous particles, whether or not there is a further layer of a material different from the material of the porous particles between the porous particles and the silicon layer or layer of silicon particles. The process of the invention proves to be particularly advantageous, since the repetition of phases 2 to 6 can be directly continued without interruption by opening the batch pressure reactor.

[0247] The silicon-containing composite particles preferably contain ≦50% by weight, more preferably ≦40% by weight, particularly preferably ≦20% by weight of additional element. The silicon-containing composite particles preferably contain ≧1% by weight, more preferably ≧3% by weight, particularly preferably ≧2% by weight of additional element. The weight percentage figures are based on the total weight of the silicon-containing composite particles. In an alternative embodiment, the silicon-containing composite particles do not contain additional elements.

[0248] In a second aspect of the present invention, a composition is provided that comprises or consists of particulate material, i.e. the silicon-containing composite particles, obtainable by the process according to the present invention.In particular, a composition is provided that comprises the silicon-containing composite particles obtainable by the process according to the present invention and at least one other component selected from (i) a binder; (ii) a conductive additive; and (iii) an additional particulate electroactive material.The composition according to the second aspect of the present invention is useful as an electrode composition and can therefore be used to form the active layer of an electrode.

[0249] The composition may be a hybrid electrode composition comprising silicon-containing composite particles and at least one additional particulate electroactive material. Examples of additional particulate electroactive materials include graphite, hard carbon, silicon, tin, germanium, aluminum and lead. The at least one additional particulate electroactive material is preferably selected from graphite and hard carbon, and most preferably, the at least one additional particulate electroactive material is graphite.

[0250] In the case of a hybrid electrode composition, the composition preferably comprises 3 to 60 wt%, or 3 to 50 wt%, or 5 to 50 wt%, or 10 to 50 wt%, or 15 to 50 wt% silicon-containing composite particles based on the total dry weight of the composition.

[0251] The at least one additional particulate electroactive material is suitably present in an amount of from 20 to 95%, or from 25 to 90%, or from 30 to 75% by weight of the at least one additional particulate electroactive material.

[0252] The at least one additional particulate electroactive material preferably has a diameter in the range of 10 to 50 μm, preferably 10 to 40 μm, more preferably 10 to 30 μm, most preferably 10 to 25 μm, for example 15 to 25 μm. 50 It has a particle size.

[0253] D of at least one additional particulate electroactive material 10The particle size is preferably at least 5 μm, more preferably at least 6 μm, more preferably at least 7 μm, more preferably at least 8 μm, more preferably at least 9 μm, and even more preferably at least 10 μm.

[0254] D of at least one additional particulate electroactive material 90 The particle size is preferably at most 100 μm, more preferably at most 80 μm, more preferably at most 60 μm, more preferably at most 50 μm, and most preferably at most 40 μm.

[0255] The at least one additional particulate electroactive material is preferably selected from carbon-containing particles, graphite particles and / or hard carbon particles, the graphite particles and hard carbon particles having a D in the range of 10 to 50 μm. 50 More preferably, the at least one additional particulate electroactive material is selected from graphite particles, the graphite particles having a D in the range of 10 to 50 μm. 50 It has a particle size.

[0256] The composition may also be a non-hybrid (or "highly loaded") electrode composition that is substantially free of additional particulate electroactive material. In this context, the term "substantially free of additional particulate electroactive material" should be interpreted as the composition containing less than 15% by weight, preferably less than 10% by weight, preferably less than 5% by weight, preferably less than 2% by weight, more preferably less than 1% by weight, more preferably less than 0.5% by weight of any additional electroactive material (i.e., additional material capable of inserting and releasing metal ions during charging and discharging of the battery), based on the total dry weight of the composition.

[0257] "Highly loaded" electrode compositions of this type preferably contain at least 50% by weight, or at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight, of silicon-containing composite particles obtained according to the process of the present invention, based on the total dry weight of the composition.

[0258] The composition may optionally include a binder. The binder functions to adhere the composition to the current collector and maintain the integrity of the composition. Examples of binders that may be used according to the present invention include polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, carboxymethyl cellulose (CMC), modified carboxymethyl cellulose (mCMC), sodium carboxymethyl cellulose (Na-CMC), polyvinyl alcohol (PVA), alginates and their alkali metal salts, styrene-butadiene rubber (SBR), and polyimides. The composition may include a mixture of binders. Preferably, the binder includes a polymer selected from polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, SBR, and CMC.

[0259] The binder may suitably be present in an amount of from 0.5 to 20% by weight, preferably from 1 to 15% by weight, preferably from 2 to 10% by weight, most preferably from 5 to 10% by weight, based on the total dry weight of the composition.

[0260] The binder may optionally be present in combination with one or more additives that modify the properties of the binder, such as crosslinking promoters, coupling agents and / or adhesion promoters.

[0261] The composition may optionally include one or more conductive additives. Preferred conductive additives are non-electroactive materials included to improve electrical conductivity between the electroactive components of the composition and between the electroactive components of the composition and the current collector. The conductive additives may be selected from carbon black, carbon fibers, carbon nanotubes, graphene, acetylene black, ketjen black, metal fibers, metal powders, and conductive metal oxides. Preferred conductive additives include carbon black and carbon nanotubes.

[0262] The one or more conductive additives may suitably be present in a total amount of from 0.5 to 20 wt %, preferably from 1 to 15 wt %, preferably from 2 to 10 wt %, most preferably from 5 to 10 wt %, based on the total dry weight of the composition.

[0263] In a third aspect, the present invention provides an electrode comprising silicon-containing composite particles obtainable by the process according to the invention, in electrical contact with a current collector. The particulate material used to manufacture the electrode of the third aspect of the invention may be in the form of a composition according to the second aspect of the invention.

[0264] As used herein, the term current collector refers to any conductive substrate capable of carrying electrical current to or from the electroactive particles in the composition. Examples of materials that can be used as current collectors include copper, aluminum, stainless steel, nickel, titanium, and sintered carbon. Copper is a preferred material. The current collector is typically in the form of a foil or mesh having a thickness between 3 and 500 μm. The particulate material of the present invention can be applied to one or both sides of the current collector, preferably to a thickness in the range of 10 μm to 1 mm, for example 20 to 500 μm, or 50 to 200 μm.

[0265] The electrode of the third aspect of the present invention can be produced by combining the silicon-containing composite particles of the present invention with a solvent and, optionally, one or more viscosity adjusting additives to form a slurry. The slurry is then cast onto the surface of a current collector, and the solvent is removed, thereby forming an electrode layer on the surface of the current collector. In addition, steps such as heat treatment for hardening the binder and calendaring of the electrode layer can be appropriately performed. The electrode layer suitably has a thickness within the range of 20 μm to 2 mm, preferably 20 μm to 1 mm, preferably 20 μm to 500 μm, preferably 20 μm to 200 μm, preferably 20 μm to 100 μm, and preferably 20 μm to 50 μm.

[0266] Alternatively, the slurry can be formed into a free-standing film or mat comprising the particulate material of the present invention, for example, by casting onto a suitable casting template, removing the solvent, and then removing the casting template. The resulting film or mat is in the form of a coherent, free-standing mass, which may then be adhered to a current collector by known methods.

[0267] The electrode of the third aspect of the invention can be used as the negative electrode of a metal-ion battery.Accordingly, in a fourth aspect, the invention provides a rechargeable metal-ion battery comprising a negative electrode comprising the electrode described above, a positive electrode comprising a positive electrode active material capable of releasing and reabsorbing metal ions, and an electrolyte between the negative electrode and the positive electrode.

[0268] The metal ions are preferably lithium ions. More preferably, the rechargeable metal ion battery of the present invention is a lithium ion battery, and the positive electrode active material is capable of releasing and reabsorbing lithium ions.

[0269] The positive electrode active material is preferably a metal oxide-based composite. Examples of suitable positive electrode active materials include LiCoO2, LiCo 0.99 Al 0.01 O2, LiNiO2, LiMnO2, LiCo 0.5 Ni 0.5 O2, LiCo 0.7 Ni 0.3 O2, LiCo 0.8 Ni 0.2 O2, LiCo 0.82 Ni 0.18 O2, LiCo 0.8 Ni 0.15 Al 0.05 O2, LiNi 0.4 Co 0.3 Mn 0.3 O2 and LiNi 0.33 Co 0.33 Mn 0.34 O2. The positive electrode current collector is generally 3 to 500 μm thick. Examples of materials that can be used as the positive electrode current collector include aluminum, stainless steel, nickel, titanium, and sintered carbon.

[0270] The electrolyte is preferably a non-aqueous electrolyte containing a metal salt, such as a lithium salt, and includes, but is not limited to, a non-aqueous electrolyte solution, a solid electrolyte, and an inorganic solid electrolyte. Examples of non-aqueous electrolyte solutions that can be used include aprotic organic solvents, such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma butyrolactone, 1,2-dimethoxyethane, 2-methyltetrahydrofuran, dimethylsulfoxide, 1,3-dioxolane, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, sulfolane, methylsulfolane, and 1,3-dimethyl-2-imidazolidinone.

[0271] Examples of organic solid electrolytes include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate ester polymers, sulfurized polyesters, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ionically dissociable groups.

[0272] Examples of inorganic solid electrolytes include lithium salts of nitrides, halides, and sulfides, such as Li5NI2, Li3N, LiI, LiSiO4, Li2SiS3, Li4SiO4, LiOH, and Li3PO4.

[0273] The lithium salt is preferably soluble in the selected solvent or mixture of solvents. Examples of suitable lithium salts include LiCl, LiBr, LiI, LiClO4, LiBF4, LiBC4O8, LiPF6, LiCF3SO3, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li and CF3SO3Li.

[0274] When the electrolyte is a non-aqueous organic solution, the metal ion battery preferably includes a separator interposed between the negative electrode and the positive electrode. The separator is typically formed of an insulating material having high ion permeability and high mechanical strength. The separator typically has a pore size of 0.01 to 100 μm and a thickness of 5 to 300 μm. An example of a suitable electrode separator is a microporous polyethylene film.

[0275] The separator may be replaced by a polymer electrolyte material, in which case the polymer electrolyte material is present in both the composite negative electrode layer and the composite positive electrode layer. The polymer electrolyte material may be a solid polymer electrolyte or a gel-type polymer electrolyte. EXAMPLES

[0276] The following examples serve to further illustrate the invention described herein.

[0277] The analytical methods and instruments used for the characteristic evaluation are as follows.

[0278] Scanning Electron Microscopy (SEM / EDX): Microscopic analysis was performed using a Zeiss Ultra 55 scanning electron microscope and an Oxford X-Max 80N energy dispersive X-ray spectrometer. Prior to analysis, a carbon vapor deposition treatment was performed using a Safematic Compact Coating Unit 010 / HV to prevent charging phenomena. Cross sections of the silicon-containing composite particles were prepared using a Leica TIC 3X ion cutter at 6 kV.

[0279] Inorganic analysis / elemental analysis: The C contents reported in the examples were confirmed using a Leco CS 230 analyzer. A Leco TCH-600 analyzer was used to determine the O and, where appropriate, N and H contents. The qualification and quantification of the other reported elements was carried out using ICP (inductively coupled plasma) optical emission spectrometry (Optima 7300 DV, Perkin Elmer). For this analysis, samples were subjected to acid digestion (HF / HNO3) in a microwave (Microwave 3000, Anton Paar). The ICP-OES measurements were performed according to ISO 11885 “Water quality-Determination of selected elements by inductively coupled plasma optical emission spectrometry (ICP-OES) (ISO 11885:2007); German version EN ISO 11885:2009” and were used for the analysis of acidic aqueous solutions (e.g. acidified samples of drinking water, wastewater and other waters, aqua regia extracts of soils and sediments).

[0280] Particle size measurement The particle size distribution was determined in the context of the present invention by static laser scattering with a Horiba LA 950 according to ISO 13320. In the preparation of the samples, particular attention must be paid to the dispersion of the particles in the measurement solution, in order not to measure the size of individual particles but the size of aggregates. For the measurements, the particles were dispersed in ethanol. For this, the dispersion before the measurements was, if necessary, treated with ultrasound at 250 W for 4 min using a Hielscher model UIS250v ultrasonic laboratory device and a LS24d5 sonotrode.

[0281] BET surface area measurement: The specific surface area of ​​the materials was measured via gas adsorption with nitrogen by the BET method (determination according to DIN ISO 9277:2003-05 with nitrogen) using a Sorptomatic 199090 instrument (Porotec) or a SA-9603MP instrument (Horiba).

[0282] Bone Density: The skeletal density, ie the density of the porous solid, which is based only on the volume of the pore space accessible to gas from the outside, was determined by He pycnometry according to DIN 66137-2.

[0283] Gurwich gas permeable pore volume: The Gurwich gas-permeable pore volume was determined according to DIN 66134 by gas adsorption measurements with nitrogen.

[0284] PD 50 Pore ​​size: PD 50 The pore size was calculated as the volumetric median pore size from the total volume of micropores defined by the Horvath-Kawazoe method according to DIN 66135 and mesopores defined by the BJH method according to DIN 66134.

[0285] The materials and equipment used in carrying out the experimental examples are as follows:

[0286] The autoclaves used consisted of a cylindrical lower part (beaker) and a lid with numerous connections (e.g. gas supply, gas removal, temperature measurement, pressure measurement). The autoclave volumes were 594 ml (AK1), 312 ml (AK2) and 5300 ml (AK3). The autoclaves were electrically heated. The stirrer used was a very close clearance helical stirrer. The height of this stirrer was approximately 50% of the clear height inside the reactor. The helical stirrer was constructed in such a way that it allowed direct temperature measurement at the bed.

[0287] The SiH4 used was grade 4.0 and was obtained from Linde GmbH.

[0288] Porous particles used: Porous particles 1 to 6 are porous carbon, porous particle 7 is porous silicon oxide, and porous particle 8 is porous boron nitride.

[0289] The compositions and specific physical properties of the porous particles 1 to 8 used are reproduced in Table 1.

[0290] Examples 1 to 23 Preparation of silicon-containing composite particles using monosilane SiH4 as silicon-containing precursor: The respective values ​​of parameters A–L, material number X of the porous particles, and type of autoclave are summarized in Table 2. In phase 1, the autoclave was filled with an amount of porous material X in Ag and closed, where K is the charge of porous particles per liter of reactor volume. In phase 2, the autoclave was first evacuated. Then, Bg of SiH4 was pressurized at a pressure C bar, where L is the charge of Si per liter of reactor volume. In phase 3, the autoclave was heated to a temperature of E °C within D minutes, and in phase 4, the temperature was maintained for F minutes. Up to time G minutes of the total heating time (D + F), there was a pressure increase according to equation 1. In the course of phase 4, the pressure increased to H bar according to equation 2. In phase 5, the autoclave was cooled to room temperature over a period of 12 hours. After this cooling, a pressure of I bar remained in the autoclave. In phase 6, the pressure in the autoclave was reduced to 1 bar, after which the autoclave was purged 5 times with nitrogen, 5 times with lean air with an oxygen fraction of 5%, 5 times with lean air with an oxygen fraction of 10%, and then 5 times with air. In phase 7, silicon-containing composite particles in the amount of Jg were isolated in the form of a fine black solid.

[0291] The analytical data obtained for the silicon-containing composite particles are summarized in Table 3. Electrochemical cells based on selected examples of the obtained silicon-containing composite particles are prepared according to Example 29. The electrochemical properties of the silicon-containing composite particles are also listed in Table 3.

[0292] [Table 1]

[0293] Table 2. Parameters of Examples 1 to 23 (nd means that it was not possible to measure for technical reasons) [Table 2]

[0294] Example 24 Production of silicon-containing composite particles by repeating phases 2 to 6: In phase 1, the autoclave (AK2) was filled with 5.0 g of porous material 1 and closed, where the charge of porous particles is 50 g per liter of reactor volume. In phase 2, the autoclave was evacuated and charged with 7 g of monosilane SiH4 (12 bar), where the charge of Si is 19.63 g per liter of reactor volume. In phase 3, the autoclave was heated to 420° C. over 65 minutes. Up to this time, the pressure increase was according to equation 1. In phase 4, this temperature was held for 180 minutes, during which the pressure increased to 68 bar according to equation 2. In phase 5, the autoclave was cooled to a temperature of 20° C. over 600 minutes. In phase 6, after the reactor pressure had fallen to 1 bar by releasing the gaseous reactor contents, in a further phase 2 the pressure was dropped to 1 mbar and the autoclave was again charged with 7 g SiH4 (12 bar), where the Si charge is now 19.63 g per liter of reactor volume. Then, in a second phase 3, the autoclave was heated to 450° C. in 70 min and in a second phase 4 this temperature was held for 240 min, during which the pressure was raised to 50 bar according to equation 2. In the last repetition of phase 6, the pressure in the autoclave was reduced to 1 mbar and the autoclave was cooled to 30° C. in 600 min, after which the gas space of the autoclave was purged 5 times with nitrogen, 5 times with lean air with an oxygen fraction of 5%, 5 times with lean air with an oxygen fraction of 10%, and then 5 times with air. In phase 7, 12.5 g of silicon-containing composite particles were isolated from the reactor in the form of a fine black powder.

[0295] The analytical data of the obtained silicon-containing composite particles are summarized in Table 3.

[0296] The silicon-containing composite particles were electrochemically characterized in a cell according to Example 29, the specifications of which are also listed in Table 3.

[0297] Example 25 Production of silicon-containing composite particles by repeating phases 2 to 6: In phase 1, the autoclave (AK3) was filled with 69 g of porous material 1 and closed, where the charge of porous particles is 40.7 g per liter of reactor volume. In phase 2, the autoclave was first evacuated and then charged with SiH4 at 300° C. (9.5 bar), where the charge of Si is 6.8 g per liter of reactor volume. In phase 3, the autoclave was heated to 420° C. over 15 min. Up to this time, the pressure increase was according to equation 1. In phase 4, this temperature was held for 30 min, during which the pressure increased to 38 bar according to equation 2. In phase 6, after a drop in the reactor pressure to 1 bar due to the release of gaseous reactor contents, the pressure was reduced to 1 mbar in a further phase 2 and the autoclave was again charged with SiH4 (11 bar), where the charge of Si is 7.9 g per liter of reactor volume. In a second phase 3, the autoclave was heated to 450° C. over 70 minutes, and in a second phase 4, this temperature was maintained for 30 minutes, during which the pressure increased to 23 bar according to equation 2. In the last repetition of phase 6, the pressure in the autoclave was reduced to 1 mbar and the autoclave was cooled to 30° C. over 600 minutes, after which the gas space of the autoclave was purged 5 times with nitrogen, 5 times with lean air with an oxygen fraction of 5%, 5 times with lean air with an oxygen fraction of 10%, and then 5 times with air. In phase 7, 140 g of silicon-containing composite particles were isolated from the reactor in the form of a fine black powder.

[0298] The analytical data of the obtained silicon-containing composite particles are summarized in Table 3.

[0299] The silicon-containing composite particles were electrochemically characterized in a cell according to Example 29, the specifications of which are also listed in Table 3.

[0300] Example 26 Preparation of silicon-containing composite particles by repeating phases 2 to 6 multiple times: In phase 1, the autoclave (AK3) was filled with 180 g of porous material 1 and closed, where the charge of porous particles was 106.1 g per liter of reactor volume. In phase 2, the autoclave was evacuated and then charged with SiH4 (9.5 bar) at a temperature of 370° C., where the charge of Si is 7.1 g per liter of reactor volume. In phase 3, the autoclave was heated to 420° C. over 10 minutes. Up to this time, the pressure increase was according to equation 1. In phase 4, this temperature was held for 30 minutes, during which the pressure increased to 24 bar according to equation 2. In phase 6, after the reactor pressure was reduced to 1 bar by releasing the gaseous reactor contents, in a further phase 2 the pressure was reduced to 1 mbar and the autoclave was again charged with SiH4 (9.5 bar), where the charge of Si is 5.6 g per liter of reactor volume. In the second phase 3, the autoclave was heated to 420° C. over 10 min, and in the second phase 4, this temperature was held for 30 min, during which the pressure increased to 22 bar according to equation 2. In the second phase 6, the reactor pressure was reduced to 1 bar by releasing the gaseous reactor contents, and then in the third phase 2, the pressure was reduced to 1 mbar and the autoclave was again charged with SiH4 (9.5 bar) at 400° C., the Si charge being 5.6 g per liter of reactor volume. In the third phase 3, the autoclave was heated to 420° C. over 10 min, and in the third phase 4, this temperature was held for 30 min, during which the pressure increased to 20 bar according to equation 2. In phase 6, the reactor pressure was reduced to 1 bar by releasing the gaseous reactor contents, then in the fourth phase 2 the pressure was reduced to 1 mbar and the autoclave was again charged with SiH4 (11 bar) at 400°C, where the Si charge was 6.4 g per litre of reactor volume. In the fourth phase 3, the autoclave was heated to 420°C over 10 min and in the fourth phase 4 this temperature was held for 30 min during which the pressure increased to 23 bar according to equation 2.In phase 6, the reactor pressure is reduced to 1 bar by releasing the gaseous reactor contents, then in the fifth phase 2, the pressure is reduced to 1 mbar and the autoclave is again charged with SiH4 at 400° C. (11 bar), the charge of Si being 6.4 g per liter of reactor volume. In the fifth phase 3, the autoclave is heated to 420° C. over 10 min, and in the fifth phase 4, this temperature is held for 30 min, during which the pressure increases to 23 bar according to equation 2. In phase 6, the reactor pressure is reduced to 1 bar by releasing the gaseous reactor contents, then in the sixth phase 2, the pressure is reduced to 1 mbar and the autoclave is again charged with SiH4 at 400° C. (11 bar), the charge of Si being 7.1 g per liter of reactor volume. In the sixth phase 3, the autoclave was heated to 420° C. over 10 minutes, and in the sixth phase 4, this temperature was maintained for 30 minutes, during which the pressure increased to 23 bar according to equation 2. In the last repetition of phase 6, the pressure in the autoclave was reduced to 1 mbar and the autoclave was cooled to 30° C. over 600 minutes, after which the gas space of the autoclave was purged 5 times with nitrogen, 5 times with lean air with an oxygen fraction of 5%, 5 times with lean air with an oxygen fraction of 10%, and then 5 times with air. In phase 7, 376 g of silicon-containing composite particles were isolated from the reactor in the form of a fine black powder.

[0301] The analytical data of the obtained silicon-containing composite particles are summarized in Table 3.

[0302] The silicon-containing composite particles were electrochemically characterized in a cell according to Example 29, the specifications of which are also listed in Table 3.

[0303] Example 27 Production of silicon-containing composite particles with multiple repetitions of Phases 2 to 6 and reaction control by reactor pressure: In phase 1, the autoclave (AK3) was filled with 180 g of porous material 1 and closed where the charge of porous particles was 106.1 g per liter of reactor volume. In phase 2, the autoclave was evacuated and SiH4 was charged (9.5 bar) at a temperature of 370 °C, where the charge of Si is 7.1 g per liter of reactor volume. In phase 3, the autoclave was heated to 420 °C over 10 minutes. Up to this time, the pressure increase was according to equation 1. In phase 4, this temperature was held for 30 minutes, during which the pressure increased to 24 bar according to equation 2. In phase 6, after the reactor pressure was reduced to 1 bar by releasing the gaseous reactor contents, the pressure was reduced to 1 mbar in a second phase 2 and the autoclave was again charged with SiH4 at 400 °C (9.5 bar), where the charge of Si is 6.1 g per liter of reactor volume. In the second phase 3, the autoclave was heated to 420° C. over 10 min, and in the second phase 4, this temperature was held for 30 min, during which the pressure increased to 21 bar according to equation 2. In phase 6, the reactor pressure was reduced to 1 bar by releasing the gaseous reactor contents, and then in the third phase 2, the pressure was reduced to 1 mbar and the autoclave was again charged with SiH4 (9.5 bar) at 400° C., the Si charge being 6.1 g per liter of reactor volume. In the third phase 3, the autoclave was heated to 420° C. over 10 min, and in the third phase 4, this temperature was held for 30 min, during which the pressure increased to 20 bar according to equation 2. In phase 6, the reactor pressure was reduced to 1 bar by releasing the gaseous reactor contents, then in the fourth phase 2 the pressure was reduced to 1 mbar and the autoclave was again charged with SiH4 (11 bar) at 400°C, where the Si charge was 7.1 g per litre of reactor volume. In the fourth phase 3, the autoclave was heated to 420°C over 10 min and in the fourth phase 4 this temperature was held for 30 min during which the pressure increased to 23 bar according to equation 2.In phase 6, the reactor pressure is reduced to 1 bar by releasing the gaseous reactor contents, then in the fifth phase 2, the pressure is reduced to 1 mbar and the autoclave is again charged with SiH4 at 400° C. (11 bar), the charge of Si being 7.1 g per liter of reactor volume. In the fifth phase 3, the autoclave is heated to 420° C. over 10 min, and in the fifth phase 4, this temperature is held for 30 min, during which the pressure increases to 23 bar according to equation 2. In phase 6, the reactor pressure is reduced to 1 bar by releasing the gaseous reactor contents, then in the sixth phase 2, the pressure is reduced to 1 mbar and the autoclave is again charged with SiH4 at 400° C. (11 bar), the charge of Si being 7.1 g per liter of reactor volume. In phase 3 of the 6th run, the autoclave was heated to 420 °C over 10 min, and in phase 4 of the 6th run, this temperature was held for 30 min, during which the pressure increased to 23 bar according to equation 2. In phase 6, the reactor pressure was reduced to 1 bar by releasing the gaseous reactor contents, and then in phase 2 of the 7th run, the pressure was reduced to 1 mbar and the autoclave was again charged with SiH4 at 400 °C (11 bar), where the Si charge was 7.1 g per liter of reactor volume. In phase 3 of the 7th run, the autoclave was heated to 420 °C over 10 min. In phase 4 of the 7th run, after 20 min, the recorded pressure increase over time was significantly reduced. The less steepness of the pressure curves indicates a smaller surface area of ​​the material, and the experiment was stopped at a pressure of 22.5 bar and the pressure in the autoclave was reduced to 1 mbar. After cooling the autoclave to 30° C. over 600 min, the gas space of the autoclave was purged 5 times with nitrogen, 5 times with lean air with an oxygen fraction of 5%, 5 times with lean air with an oxygen fraction of 10%, and then 5 times with air. In phase 7, 439 g of silicon-containing composite particles were isolated from the reactor in the form of a fine black powder.

[0304] The analytical data of the obtained silicon-containing composite particles are summarized in Table 3.

[0305] The silicon-containing composite particles were electrochemically characterized in a cell according to Example 29, the specifications of which are also listed in Table 3.

[0306] Example 28 Preparation of silicon-containing composite particles with in-situ carbon coating: In phase 1, the autoclave (AK2) was filled with 8 g of porous material 1 and closed, where the charge of porous particles is 80.1 g per liter of reactor volume. In phase 2, the autoclave was first evacuated and then charged with SiH4 (16 bar), where the charge of Si is 7.1 g per liter of reactor volume. In phase 3, the autoclave was heated to 420° C. over 40 minutes. Up to this time, the pressure increase was according to equation 1. In phase 4, this temperature was held for 170 minutes, during which the pressure increased to 85 bar according to equation 2. In phase 5, the autoclave was cooled to a temperature of 20° C. over 600 minutes. In phase 6, after the drop in the reactor pressure to 1 bar due to the release of gaseous reactor contents, the pressure was reduced to 1 mbar in the second phase 2 and the autoclave was charged with 2 g of liquid styrene. In a second phase 3, the autoclave was heated to 650° C. over 90 minutes, and in a second phase 4, this temperature was maintained for 120 minutes. In phase 6, the pressure in the autoclave was reduced to 1 bar and then purged 5 times with nitrogen, 5 times with lean air with an oxygen fraction of 5%, 5 times with lean air with an oxygen fraction of 10%, and then 5 times with air. In phase 7, 17.3 g of silicon-containing composite particles were isolated from the reactor in the form of a fine black powder.

[0307] The analytical data of the obtained silicon-containing composite particles are summarized in Table 3.

[0308] The silicon-containing composite particles were electrochemically characterized in a cell according to Example 29, the specifications of which are also listed in Table 3.

[0309] Example 29 Electrochemical characterization of silicon-containing composite particles for use as active materials in the negative electrodes of lithium-ion batteries: 29.71 g of polyacrylic acid (dried to constant weight at 85 °C; Sigma-Aldrich, Mw ~ 450000 g / mol) and 756.6 g of deionized water were stirred on a shaker (290 / min) for 2.5 h until the polyacrylic acid was completely dissolved. Lithium hydroxide monohydrate (Sigma-Aldrich) was added in portions to the solution until the pH was 7.0 (measured using a WTW pH 340ipH meter with SenTix RJD probe). Subsequently, 3.87 g of the neutralized polyacrylic acid solution and 0.96 g of graphite (Imerys, KS6L C) were introduced into a 50 ml vessel and mixed at 2000 rpm in a planetary mixer (SpeedMixer, DAC 150 SP) and then mixed on a shaker for another 4 h. Next, 3.40 g of silicon-containing composite particles of each of Examples 1, 6, 7, 9, 10, 11, 22, 23, 27 or 30 were stirred at 2000 rpm for 1 minute. Then, 1.21 g of an 8% dispersion of conductive carbon black and 0.8 g of deionized water were added and incorporated on a planetary mixer at 2000 rpm. Their dispersion was carried out in a dissolver at 3000 rpm and at a constant temperature of 20° C. for 30 minutes. The ink was again degassed under reduced pressure in a planetary mixer at 2500 rpm for 5 minutes. The completed dispersion was then applied on a copper foil (Schlenk Metallfolien, SE-Cu58) with a thickness of 0.03 mm using a film applicator frame (Erichsen, model 360) with a gap height of 0.1 mm. The anode coating thus produced was then dried at 50° C. for 60 minutes under an air pressure of 1 bar. The average dried anode coating basis weight is 1.9 mg / cm 2 and the coating density is 0.9 g / cm 3 It was.

[0310] The electrochemical studies were carried out using a button cell (type CR2032, Horsen Corporation) with a two-electrode configuration. The electrode coating was used as the counter or negative electrode (Dm = 15 mm) and the coating based on lithium nickel manganese cobalt oxide 6:2:2 (content 94.0%, average basis weight 15.9 mg / cm2) was 2, obtained from the company SEI) was used as the working or positive electrode (Dm = 15 mm). A glass fiber filter paper (Whatman, GD type D) impregnated with 60 μl of electrolyte was used as the separator (Dm = 16 mm). The electrolyte was a 1.0 molar solution of lithium hexafluorophosphate in a 1:4 (v / v) mixture of fluoroethylene carbonate and diethyl carbonate. The cell was assembled in a glove box (<1 ppm H2O, O2). The moisture content of the dry mass of all components used was less than 20 ppm.

[0311] Electrochemical tests were performed at 20°C. The cells were charged by cc / cv (constant current / constant voltage) method at a constant current of 5 mA / g (corresponding to C / 25) in the first cycle and 60 mA / g (corresponding to C / 2) in the subsequent cycles, and charged at a constant voltage until the current dropped below 1.2 mA / g (corresponding to C / 100) or 15 mA / g (corresponding to C / 8) after reaching the voltage limit of 4.2 V. The cells were discharged by cc (constant current) method at a constant current of 5 mA / g (corresponding to C / 25) in the first cycle and 60 mA / g (corresponding to C / 2) in the subsequent cycles, until the voltage limit of 2.5 V was reached. The specific current selected was based on the weight of the coating on the positive electrode. The ratio of the cell charge capacity to the cell discharge capacity is called the coulombic efficiency. The electrodes were selected to have a positive to negative capacity ratio of 1:1.2.

[0312] The results of electrochemical testing of full cells of lithium ion batteries containing the active materials of Examples 1, 6, 7, 9, 10, 11, 22, 23, 27 or 30 are shown in Table 3.

[0313] Comparative Example 30 Production of silicon-containing composite particles

[0314] Into a tubular reactor having a volume of 1 L, 2.2 g of the porous particles 1 were introduced, and the tubular reactor was closed. The tubular reactor was then heated to a temperature of 410° C. and circulated with a gas flow of 10% SiH4 in nitrogen for 5 hours. After cooling, 5.24 g of silicon-containing composite particles were isolated in the form of a black powder.

[0315] The resulting product had a silicon content of 56% by mass (ICP) and a surface area of ​​9 m 2 / g, density 2.16g / cm 3 (He pycnometry), and the oxygen content was 8.76 mass%.

[0316] Electrochemical testing was carried out on a full cell lithium ion battery according to Example 29. The corresponding results are also listed in Table 3. [Brief description of the drawings]

[0317] [Figure 1] FIG. 1 shows an SEM micrograph of a cross section of a silicon-containing composite particle of Example 1.

[0318] [Diagram 2] FIG. 2 shows an SEM micrograph of a cross section of the silicon-containing composite particle of Comparative Example 30.

[0319] In Comparative Example 30, 5.24 g of material was produced in a reactor having a volume of 1000 ml over the course of 300 minutes by a method not according to the invention (without a heating step). In Example 1, 11.4 g of material was produced in a reactor having a volume of 312 ml over the course of 195 minutes by a method according to the invention. Accordingly, in Example 1, the yield of material was 10.7 times greater in relation to time and reactor volume compared to that in Example 30.

[0320] Furthermore, a comparison of the SEM micrographs of the cross-sections of the materials of Example 1 and Comparative Example 30 reveals that the material produced in Example 1 has a higher homogeneity in terms of interparticle silicon content. The indicator is the color tone of the individual particles on the SEM micrograph. A lighter color tone indicates a higher silicon content relative to all other particles, and a darker color tone indicates a lower silicon content relative to all other particles. Similar gray stages of two or more particles indicate similar silicon content. From this, it is clear that silicon-containing composite particles can be obtained much more quickly by the method of the present invention, and are further characterized by a very homogeneous deposition of silicon in the pores and on the surface of the porous particles, and are particularly suitable for use as an active material in negative electrodes for lithium-ion batteries due to their stability and electrochemical properties.

[0321] [Table 3]

Claims

1. 1. A method for producing silicon-containing composite particles, the method comprising the steps of: (a) providing a plurality of porous particles comprising micropores and / or mesopores, (i) D of the porous particles 50 The particle size is within the range of 0.5 to 200 μm, (ii) the total pore volume of the micropores and mesopores as measured by gas adsorption is between 0.4 and 2.2 cm 3 / g, (iii) PD measured by gas adsorption 50 The pore size is 30 nm or less; (b) combining the charge of porous particles with a charge of silicon-containing precursor in a batch pressure reactor, wherein the charge of porous particles is mixed with a reactor volume (cm 3 / L RV ) At least 20 cm per liter 3 and the charge of silicon-containing precursor is greater than the reactor volume (cm 3 / L RV ) containing at least 2 g of silicon per liter; (c) heating the reactor to a temperature effective to cause deposition of silicon within the pores of the porous particles, thereby providing the silicon-containing composite particles; A method comprising:

2. The method of claim 1 , wherein the one or more porous particles are porous conductive particles.

3. The method of claim 1 or 2, wherein the porous particles are porous carbon particles.

4. The porous particles have a D in the range of 0.5 to 150 μm, or 0.5 to 100 μm, or 0.5 to 50 μm, or 0.5 to 30 μm, or 1 to 25 μm, or 1 to 20 μm, or 2 to 25 μm, or 2 to 20 μm, or 2 to 18 μm, or 3 to 20 μm, or 3 to 18 μm, or 3 to 15 μm, or 4 to 18 μm, or 4 to 15 μm, or 4 to 12 μm, or 5 to 15 μm, or 5 to 12 μm, or 5 to 10 μm, or 5 to 8 μm. 50 The method according to any one of claims 1 to 3, wherein the particle size is 0.01 to 0.

5.

5. The porous particles are 0.45 to 2.2 cm 3 / g, or 0.5 to 2 cm 3 / g, or 0.55 to 2 cm 3 / g, or 0.6 to 1.8 cm 3 / g, or 0.65 to 1.8 cm 3 / g, or 0.7 to 1.6 cm 3 / g, or 0.75 to 1.6 cm 3 / g, or 0.8 to 1.5 cm 3 The method of any one of claims 1 to 4, wherein the total volume of micropores and mesopores is in the range of 1 / g.

6. PD of the porous particles 50 The method of any one of claims 1 to 5, wherein the pore size is 25 nm or less, or 20 nm or less, or 15 nm or less, or 12 nm or less, or 10 nm or less, or 8 nm or less, or 6 nm or less, or 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less, or 1.5 nm or less.

7. A method according to any one of claims 1 to 6, wherein the volume ratio of micropores to mesopores is from 90:10 to 55:45, or from 90:10 to 60:40, or from 85:15 to 65:

35.

8. The porous particles are 750 mm 2 / g to 4,000m 2 / g, or 1,000m 2 / g~3,500m 2 / g, or 1,250m 2 / g~3,250m 2 / g, or 1,500m 2 / g to 3,000m 2 The method of any one of claims 1 to 7, wherein the SiO2 has a BET surface area in the range of 0.1 to 0.5 μm / g.

9. The method of any one of claims 1 to 8, wherein the silicon-containing precursor is a silicon-containing liquid or gas at 100 kPa and 20°C.

10. The silicon-containing precursor is silane (SiH 4 ), disilane (Si 2 H 6 ), trisilane (Si 3 H 8 9. The method of claim 8, wherein the silane is selected from methylsilane, dimethylsilane and chlorosilane.

11. The charge of porous particles used in step (b) is at least 200 cm 3 / L RV , or at least 250 cm 3 / L RV , or at least 300 cm 3 / L RV , or at least 400 cm 3 / L RV , or at least 500 cm 3 / L RV , or at least 600 cm 3 / L RV , or at least 700 cm 3 / L RV , or at least 800 cm 3 / L RV , or at least 900 cm 3 / L RV The method according to any one of claims 1 to 10, wherein the volume of the mixture is 0.01 to 0.

15.

12. The charge of silicon-containing precursor used in step (b) is at least 5 g / L. RV of silicon, or at least 10 g / L RV of silicon, or at least 15 g / L RV of silicon, or at least 20 g / L RV of silicon, or at least 40 g / L RV of silicon, or at least 60 g / L RV of silicon, or at least 80 g / L RV of silicon, or at least 100 g / L RV of silicon, or at least 150 g / L RV of silicon, or at least 200 g / L RV of silicon, or at least 250 g / L RV The method according to any one of claims 1 to 11, comprising the step of:

13. The method of any one of claims 1 to 12, wherein the batch pressure reactor is essentially free of oxygen gas.

14. 14. The method of any one of claims 1 to 13, wherein step (b) further comprises adding a charge of an inert padding gas to the batch pressure reactor.

15. 15. The method of any one of claims 1 to 14, wherein the contents of the batch pressure reactor of step (b) consist essentially of the porous particles, the silicon-containing precursor, and optionally an inert padding gas or hydrogen.

16. The method according to any one of claims 1 to 15, wherein the mass ratio (based on silicon) of the porous particles to the silicon-containing precursor in step (b) is 95:5 to 40:

60.

17. 17. The process of any one of claims 1 to 16, wherein the temperature in step (c) is in the range of 300 to 800°C, or 300 to 750°C, or 300 to 700°C, or 300 to 650°C, or 300 to 600°C, or 320 to 550°C, or 320 to 500°C, or 340 to 450°C, or 350 to 450°C, or 300 to 395°C, or 320 to 380°C.

18. A process according to any one of the preceding claims, wherein the pressure in step (c) is at least 200 kPa, or at least 300 kPa, or at least 500 kPa.

19. 19. The method of any one of the preceding claims, wherein the pressure in step (c) is at least 700 kPa, or at least 1,000 kPa, or at least 1,500 kPa, or at least 2,000 kPa, or at least 2,500 kPa, or at least 3,000 kPa, or at least 4,000 kPa, or at least 5,000 kPa.

20. The method of any one of claims 1 to 19, wherein step (c) is carried out at or above the critical pressure of the silicon-containing precursor.

21. The method of any one of claims 1 to 19, wherein step (c) is carried out below the critical pressure of the silicon-containing precursor.

22. The method of any one of claims 1 to 21, wherein the porous particles are agitated during step (c).

23. 23. The method according to any one of claims 1 to 22, wherein in step c) the reactor is heated to a temperature effective to cause deposition of silicon within the pores of the porous particles and on the surfaces of the porous particles.

24. The following steps: (d) venting by-product gas from the batch pressure reactor; (e) adding an additional charge of silicon-containing precursor to the batch pressure reactor, wherein the additional charge of silicon-containing precursor gas is greater than or equal to the reactor volume (g / L) RV ) containing at least 2 g of silicon per liter; (f) heating the reactor to a temperature effective to cause further deposition of silicon in the pores of the porous particles; The method of any one of claims 1 to 23, further comprising:

25. 25. The method of claim 24, wherein steps (d)-(f) are repeated one or more times.

26. The following steps: (g) contacting the surfaces of the composite particles from steps (c) through (f) with a passivation agent, wherein the composite particles are not exposed to oxygen prior to contacting with the passivation agent; The method of any one of claims 1 to 25, further comprising:

27. The following steps: (h) combining the composite particles from step (c), step (f) or step (g) with a pyrolytic carbon precursor; (i) heating the pyrolytic carbon precursor to a temperature effective to cause deposition of pyrolytic conductive carbon material within the pores and / or on the surfaces of the composite particles; The method of any one of claims 1 to 26, further comprising:

28. The following steps a) to c) are performed in the following process phases 1 to 7: Phase 1: Packing the batch pressure reactor with one or more types of porous particles; Phase 2: charging the batch pressure reactor with one or more silicon-containing precursors; Phase 3: Heating the batch pressure reactor to a target temperature at which the silicon-containing precursor begins to decompose within the batch pressure reactor; Phase 4: Decomposing the silicon-containing precursor and depositing silicon within the pores of the porous particles and, optionally, on the surfaces of the porous particles, thereby providing the silicon-containing composite particles; Phase 5: Cooling the batch pressure reactor; Phase 6: Removing gaseous reaction products formed during deposition from the batch pressure reactor; Phase 7: Removing the silicon-containing composite particles from the batch pressure reactor; is divided into 24. The process according to any one of claims 1 to 23, characterized in that during phase 4 the pressure in the batch pressure reactor increases to at least 7 bar.

29. A method for producing silicon-containing composite particles by pyrolysis of one or more silicon-containing precursors in the presence of one or more porous particles, wherein silicon is deposited within the pores of the porous particles and, optionally, on the surfaces of the porous particles, the method comprising at least the following phases 1 to 7: Phase 1: Packing a batch pressure reactor with one or more types of porous particles, the charge of porous particles being equal to or greater than the reactor volume (cm 3 / L RV ) At least 20 cm per liter 3 and the porous particles contain micropores and / or mesopores; (i) D of the porous particles 50 The particle size is within the range of 0.5 to 200 μm, (ii) the total pore volume of the micropores and mesopores as measured by gas adsorption is between 0.4 and 2.2 cm 3 / g, (iii) PD measured by gas adsorption 50 The pore size is 30 nm or less; Phase 2: Charging the batch pressure reactor with one or more silicon-containing precursors, wherein the charge of silicon-containing precursors is greater than or equal to the reactor volume (g / L). RV ) containing at least 2 g of silicon per liter; Phase 3: Heating the batch pressure reactor to a target temperature at which the silicon-containing precursor begins to decompose within the batch pressure reactor; Phase 4: Decomposing the silicon-containing precursor and depositing silicon within the pores of the porous particles and, optionally, on the surfaces of the porous particles, thereby providing the silicon-containing composite particles; Phase 5: Cooling the batch pressure reactor; Phase 6: Removing gaseous reaction products formed during deposition from the batch pressure reactor; Phase 7: Removing the silicon-containing composite particles from the batch pressure reactor; is divided into During phase 4, the pressure in the batch pressure reactor is increased to at least 7 bar.

30. During phase 4, the pressure in the batch pressure reactor changes, which occurs as a result of the change in mass of material as a result of the decomposition of the silicon-containing precursor and deposition of silicon, and optionally, the temperature change in the batch pressure reactor, and the pressure change is preferably expressed by the following formula: [0010] 30. The method according to claim 28 or 29,

31. The pressure in the batch pressure reactor is increased in phase 3 and phase 4, the pressure increase in phase 4 being higher than the pressure increase in phase 3, preferably according to the following formula: [0025] The method according to any one of claims 28 to 30,

32. 32. The process of any one of claims 28 to 31, wherein the temperature in the batch pressure reactor in phase 4 is in the range of 100 to 1000°C.

33. 33. The process of any one of claims 28 to 32, wherein the pressure in the batch pressure reactor in phase 4 is in the range of 10 to 400 bar.

34. The method according to any one of claims 28 to 33, wherein phase 1 is followed by at least two iterations of the procedure consisting of phases 2 to 5 and optionally phase 6, after which only phase 7 is performed.

35. 35. The method of claim 34, wherein in at least one phase 2, one or more silicon-containing precursors are used, and in at least one further phase 2, one or more carbon precursors and no silicon-containing precursors are used.

36. The method of any one of claims 28 to 35, wherein phase 4 is carried out isothermally.

37. 36. The method of any one of claims 28 to 35, wherein phase 4 is not carried out isothermally and the batch pressure reactor is heated or cooled.

38. 32. The method of claim 30 or 31, wherein the progress of the silicon deposition is monitored based on pressure changes.

39. 39. The method of claim 38, wherein phase 4 ends when or after the pressure increase in phase 4 disappears.

Citation Information

Patent Citations

  • Electroactive materials for metal-ion batteries

    GB2580110A

  • A method for forming an anode for a lithium-ion battery by depositing silicon onto a carbon material.

    JP2010525549A

  • Mechanical fluidized reactor system and method suitable for silicon production

    JP2013539823A

  • Novel material having highly durable lithium insertion and method for manufacturing the same

    JP2018534720A

  • Decomposition of silicon-containing precursors onto porous scaffolds

    JP2020514231A